Phase difference film, optical laminate, polarizing plate, image display device
Patent Information
- Application Number
- CN202580020834.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-27
- Filing Date
- 2025-03-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0040]根据本发明,能够提供一种相位差膜,其在与UV粘接剂接触而实施基于紫外线照射的固化处理时,与通过UV粘接剂的固化而形成的UV粘接层之间的附着性优异。
Smart Images

Figure CN122996355A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a phase retardation film, an optical laminate, a polarizer, and an image display device. Background Technology
[0002] Optical films such as optical compensation films and phase difference films are used in various image display devices to eliminate image coloration or expand the field of view.
[0003] Stretched birefringent films have been used as optical films, but in recent years, it has been proposed to use optical films with optical anisotropy layers formed by liquid crystal compounds to replace stretched birefringent films.
[0004] Optical anisotropic layers formed from liquid crystal compounds are typically formed by coating a liquid crystal composition containing a liquid crystal compound to form a liquid crystal composition layer, and then aligning the liquid crystal composition layer.
[0005] In liquid crystal composition layers, leveling agents are sometimes added to improve the surface properties of the layer surface. For example, Patent Document 1 discloses a liquid crystal composition layer in which a fluorine-based leveling agent containing fluorine atoms is added.
[0006] Previous technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2023-108591 Summary of the Invention
[0007] The technical problem to be solved by the invention
[0008] In recent years, due to the persistent degradation and toxicity of PFAS (perfluoroalkyl and polyfluoroalkyl compounds), there has been progress in restricting PFAS, and research is underway on alternatives that do not use fluorine atoms. As a representative example, research is being conducted on alternative materials containing silicon atoms. Along with these restrictions, leveling agents containing silicon atoms are being researched.
[0009] Furthermore, in recent years, there has been a need for a retardation film with excellent adhesion to an adhesive layer (hereinafter referred to as a "UV adhesive layer") formed by curing a UV-curable adhesive (hereinafter also referred to as a "UV adhesive"). More specifically, there is a need for a retardation film with excellent adhesion to a UV adhesive layer formed by curing a UV adhesive when subjected to UV-based curing treatment in contact with a UV adhesive. In particular, it is desirable for the retardation film to have excellent adhesion to a UV adhesive layer formed by curing a UV adhesive containing a cationic polymeric compound.
[0010] Against the background described above, the inventors have discovered that there is still room for research on phase retardation films that use leveling agents containing silicon atoms and exhibit excellent adhesion to UV adhesive layers.
[0011] Therefore, the technical challenge of the present invention is to provide a phase difference film that exhibits excellent adhesion to a UV adhesive layer formed by curing the UV adhesive when it is subjected to UV-based curing treatment in contact with a UV adhesive.
[0012] Furthermore, the technical challenge of this invention lies in providing an optical laminate with excellent adhesion between the phase retardation layer and the UV adhesive layer.
[0013] Furthermore, the technical challenge of the present invention also lies in providing a polarizer and an image display device having the above-described optical laminate.
[0014] means for solving technical problems
[0015] In order to solve the above-mentioned technical problems, the inventors conducted in-depth research and found that the technical problems can be solved by the following configuration.
[0016] [1] A phase retardation film, which is a phase retardation film obtained by free radical polymerization of a composition comprising a free radical polymerizable liquid crystal compound and a polymer, wherein, The polymer described above has repeating units containing silicon atoms, repeating units containing cationic polymerizable groups, and repeating units containing free radical polymerizable groups.
[0017] [2] According to the phase difference film of [1], wherein the repeating unit containing silicon atoms has a group represented by formula (Ia-1) as described later.
[0018] [3] The phase difference film according to [1] or [2], wherein the repeating unit containing silicon atoms has a group represented by formula (Ib) described later.
[0019] [4] The phase difference film according to any one of [1] to [3], wherein in the repeating unit containing the free radical polymerizable group, the free radical polymerizable group is a polymerizable group having an unsaturated double bond group, and the length from the main chain to the unsaturated double bond group contained in the free radical polymerizable group is 7 atoms or more.
[0020] [5] The phase difference film according to any one of [1] to [4], wherein the repeating unit containing the free radical polymerizable group is a repeating unit represented by formula (Z-1) described later.
[0021] [6] The phase difference film according to any one of [1] to [5], wherein in the repeating unit containing the cationic polymeric group, the length from the main chain to the cationic polymeric group is 8 atoms or more.
[0022] [7] The phase difference film according to any one of [1] to [6], wherein the free radical polymerizable liquid crystal compound is at least one selected from the group consisting of free radical polymerizable rod-shaped liquid crystal compounds and free radical polymerizable disk-shaped liquid crystal compounds.
[0023] [8] The phase difference film according to any one of [1] to [7], wherein, In the above polymers, The content of the aforementioned repeating units containing silicon atoms is 30–80% by mass relative to the total number of repeating units in the polymer. The content of the repeating units containing cationic polymeric groups is 3-30% by mass relative to the total number of repeating units in the polymer. The content of the repeating units containing free radical polymerizable groups is 3 to 30 by mass relative to the total number of repeating units in the polymer.
[0024] [9] The phase difference film according to any one of [1] to [8], wherein, In the above polymers, The content of the aforementioned repeating units containing silicon atoms is 50-70% by mass relative to the total number of repeating units in the polymer. The content of the repeating units containing cationic polymeric groups is 5-15% by mass relative to the total number of repeating units in the polymer. The content of the repeating units containing free radical polymerizable groups is 5 to 15 by mass relative to the total number of repeating units in the polymer.
[0025]
[10] An optical laminate comprising a retardation layer and an adhesive layer formed by curing an ultraviolet-curable adhesive, wherein, The aforementioned phase retardation layer comprises: a cured product of a free radical polymerizable liquid crystal compound; and a cured product derived from a polymer biased towards the adhesive layer side, the polymer having repeating units comprising silicon atoms, repeating units comprising cationic polymerizable groups, and repeating units comprising free radical polymerizable groups.
[0026]
[11] According to the optical laminate of
[10] , wherein the adhesive layer is a layer formed by curing an ultraviolet-curable adhesive containing an epoxy compound, and the cationic polymeric group contained in the polymer is an epoxy group.
[0027]
[12] The optical laminate according to
[10] or
[11] , wherein the repeating unit containing silicon atoms contained in the polymer has a group represented by formula (Ia-1) described later.
[0028]
[13] An optical laminate according to any one of
[10] to
[12] , wherein the repeating unit containing silicon atoms contained in the polymer has a group represented by formula (Ib) described later.
[0029]
[14] An optical laminate according to any one of
[10] to
[13] , wherein in the repeating unit containing a free radical polymerizable group, the free radical polymerizable group is a polymerizable group having an unsaturated double bond group, and the length from the main chain to the unsaturated double bond group contained in the free radical polymerizable group is 7 atoms or more.
[0030]
[15] An optical laminate according to any one of
[10] to
[14] , wherein the repeating unit contained in the polymer and the repeating unit containing the free radical polymerizable group is a repeating unit represented by formula (Z-1) described later.
[0031]
[16] An optical laminate according to any one of
[10] to
[15] , wherein in the repeating unit containing cationic polymeric groups contained in the polymer, the length from the main chain to the cationic polymeric group is 8 atoms or more.
[0032]
[17] An optical laminate according to any one of
[10] to
[16] , wherein the free radical polymerizable liquid crystal compound is at least one free radical polymerizable liquid crystal compound selected from the group consisting of free radical polymerizable rod-shaped liquid crystal compounds and free radical polymerizable disk-shaped liquid crystal compounds.
[0033]
[18] An optical laminate according to any one of
[10] to
[17] , wherein, In the above polymers, The content of the aforementioned repeating units containing silicon atoms is 30–80% by mass relative to the total number of repeating units in the polymer. The content of the repeating units containing cationic polymeric groups is 3-30% by mass relative to the total number of repeating units in the polymer. The content of the repeating units containing free radical polymerizable groups is 3 to 30 by mass relative to the total number of repeating units in the polymer.
[0034]
[19] An optical laminate according to any one of
[10] to
[18] , wherein, In the above polymers, The content of the aforementioned repeating units containing silicon atoms is 50-70% by mass relative to the total number of repeating units in the polymer. The content of the repeating units containing cationic polymeric groups is 5-15% by mass relative to the total number of repeating units in the polymer. The content of the repeating units containing free radical polymerizable groups is 5 to 15 by mass relative to the total number of repeating units in the polymer.
[0035]
[20] A polarizer having an optical laminate and a polarizer as described in any one of
[10] to
[19] .
[0036]
[21] An image display device comprising the polarizer described in
[20] .
[0037]
[22] The image display device according to
[21] is an organic electroluminescent display device.
[0038]
[23] The image display device according to
[21] is a liquid crystal display device.
[0039] Invention Effects
[0040] According to the present invention, a phase retardation film can be provided which exhibits excellent adhesion to a UV adhesive layer formed by curing the UV adhesive when subjected to UV-based curing treatment in contact with a UV adhesive.
[0041] Furthermore, according to the present invention, an optical laminate with excellent adhesion between the phase retardation layer and the UV adhesive layer can be provided.
[0042] Furthermore, according to the present invention, it is possible to provide a polarizer and an image display device having the above-described optical laminate. Attached Figure Description
[0043] Figure 1 This is a schematic cross-sectional view illustrating an example of the optical laminate of the present invention.
[0044] Figure 2 This is a schematic cross-sectional view illustrating an example of the optical laminate of the present invention.
[0045] Figure 3 This is a schematic cross-sectional view illustrating an example of the optical laminate of the present invention.
[0046] Figure 4 This is a schematic cross-sectional view showing an example of a polarizer incorporating the optical laminate of the present invention. Detailed Implementation
[0047] The present invention will now be described in detail.
[0048] The following description of the constituent elements is sometimes based on representative embodiments of the present invention, but the present invention is not limited to such embodiments.
[0049] In this specification, the numerical range indicated by “~” refers to the range encompassed by the values recorded before and after “~” as the lower and upper limits.
[0050] Furthermore, in this specification, when there are two or more components, the “content” of that component refers to the total content of these two or more components.
[0051] In this specification, for numerical ranges described in stages, the upper or lower limit value recorded in a certain numerical range can be replaced with the upper or lower limit value of other numerical ranges described in stages. Furthermore, within the numerical ranges described in this specification, the upper or lower limit value recorded in a certain numerical range can be replaced with the values shown in the embodiments.
[0052] In this specification, a combination of two or more preferred methods is a more preferred method.
[0053] In this specification, unless otherwise specified, the bonding direction of the divalent groups (e.g., -CO-O-) is not limited. For example, in a compound represented by the formula "XYZ" where Y is -CO-O-, the compound can be "XO-CO-Z" or "X-CO-OZ".
[0054] In this specification, "(meth)acrylic acid / group" includes both acrylic acid / group and methacrylic acid / group, "(meth)acryloyl group" includes both acryloyl group and methacryloyl group, "(meth)acrylate" includes both acrylate and methacrylate, and "(meth)acrylonitrile" includes both acrylonitrile and methacrylonitrile.
[0055] In this specification, "organic group" refers to a group having one or more carbon atoms. The organic group is preferably a monovalent group.
[0056] In this specification, unless otherwise specified, the slow axis is defined at 550nm.
[0057] In this specification, Re(λ) and Rth(λ) represent the in-plane delay and the thickness direction delay at wavelength λ, respectively. Unless otherwise specified, wavelength λ is set to 550 nm.
[0058] Furthermore, in this specification, Re(λ) and Rth(λ) are values measured at wavelength λ using an AxoScan OPMF-1 (manufactured by Opto Science).
[0059] Specifically, by inputting the average refractive index ((nx+ny+nz) / 3) and film thickness (d(μm)) into AxoScan OPMF-1, the following values are calculated: Slow axis direction (°) Re(λ) = R0(λ) Rth(λ)=((nx+ny) / 2-nz)×d.
[0060] In addition, although R0(λ) is displayed as a value calculated by AxoScan OPMF-1, its meaning refers to Re(λ).
[0061] In this specification, the relationship of angles (e.g., "orthogonal", "parallel", etc.) includes the range of errors permissible in the technical field to which this invention pertains. Specifically, it refers to a range within ±10° of a strict angle, preferably within ±5° or less, and more preferably within ±3° or less of a strict angle.
[0062] In this specification, solid components refer to film-forming components and do not include solvents. Any component that forms a film is considered a solid component even if it is in liquid form.
[0063] [Phase difference film]
[0064] The phase difference film of the present invention will now be described in detail.
[0065] The phase retardation film of the present invention is a phase retardation film obtained by free radical polymerization of a composition comprising a free radical polymerizable liquid crystal compound and a polymer (hereinafter also referred to as a "specific leveling agent") (hereinafter also referred to as a "liquid crystal composition"). Certain leveling agents have repeating units containing silicon atoms, repeating units containing cationic polymeric groups, and repeating units containing free radical polymeric groups.
[0066] While the reason why the phase retardation film with the above-described structure can solve the technical problem of the present invention is not clear, the inventors speculate as follows.
[0067] Furthermore, the mechanism by which the effect is achieved is not limited by the following conjecture. In other words, even if the effect is achieved through a mechanism other than that described below, it is still included within the scope of this invention.
[0068] The phase retardation film of the present invention is a phase retardation film formed by curing a liquid crystal composition comprising a free radical polymerizable liquid crystal compound and a specific leveling agent through free radical polymerization. The phase retardation film of the present invention typically comprises a cured product of a free radical polymerizable liquid crystal compound and a cured product of a specific leveling agent. To exhibit the desired phase retardation function, the orientation state of the liquid crystal compound is immobilized. In the above-described phase retardation film, the cured product of the specific leveling agent is present biased on the surface of the phase retardation film and has cationic polymerizable groups derived from the specific leveling agent that have not participated in the free radical polymerization reaction.
[0069] With the above-described configuration, the phase retardation film of the present invention, when subjected to UV-based curing treatment with a UV adhesive in contact with it, readily forms a strong bond between the cationic polymeric groups of the cured product of a specific leveling agent on the surface of the phase retardation film and the UV adhesive. As a result, it readily exhibits excellent adhesion to the UV adhesive layer formed by curing the UV adhesive. Therefore, for example, when a laminate formed by stacking a phase retardation film and a substrate (e.g., a film with a liquid crystal layer or a polarizer) with a UV adhesive is subjected to UV-based curing treatment, the cationic polymeric groups of the cured product of a specific leveling agent on the surface of the phase retardation film readily form a strong bond with the UV adhesive. As a result, it readily exhibits excellent adhesion to the UV adhesive layer formed by curing the UV adhesive.
[0070] Hereinafter, the superior adhesion between the phase difference film and the UV adhesive layer of the present invention will be referred to as "superior effect of the present invention".
[0071] Hereinafter, the liquid crystal composition used to form the retardation film of the present invention, the method for manufacturing the retardation film, and the characteristics of the retardation film will be described in this order.
[0072] [Liquid Crystal Composition]
[0073] The liquid crystal composition comprises a free radical polymerizable liquid crystal compound and a specific leveling agent.
[0074] <Free radical polymerizable liquid crystal compounds>
[0075] Free radical polymerizable liquid crystal compounds are liquid crystal compounds containing free radical polymerizable groups. The orientation state of free radical polymerizable liquid crystal compounds can be fixed by free radical polymerization after orientation.
[0076] There are no particular limitations on the free radical polymerizable groups mentioned above. Examples include vinyl, allyl, vinyloxy, maleimide, allyloxy, (meth)acryloyl, (meth)acryloyloxy, and (meth)acrylamide.
[0077] The number of free radical polymerizable groups in the free radical polymerizable liquid crystal compound is preferably one or more, more preferably two or more. Furthermore, as an upper limit, there is no limitation, but it is preferably ten or less, more preferably six or less, and even more preferably three or less.
[0078] Liquid crystal compounds are typically classified into rod-shaped and disc-shaped types based on their shape. Furthermore, each type has low-molecular-weight and high-molecular-weight forms. A high-molecular-weight compound generally refers to a substance with a degree of polymerization of 100 or higher (Polymer Physics and Phase Transition Dynamics, Masao Doi, p. 2, Iwanami Shoten, 1992). In this invention, any liquid crystal compound can be used, but rod-shaped or disc-shaped liquid crystal compounds (disc-shaped liquid crystal compounds) are preferred.
[0079] The free radical polymerizable liquid crystal compound contained in the liquid crystal composition is preferably at least one of the group consisting of free radical polymerizable rod-shaped liquid crystal compounds and free radical polymerizable disk-shaped liquid crystal compounds.
[0080] The liquid crystal composition may use two or more free radical polymerizable rod-shaped liquid crystal compounds, two or more free radical polymerizable disk-shaped liquid crystal compounds, or a mixture of free radical polymerizable rod-shaped liquid crystal compounds and free radical polymerizable disk-shaped liquid crystal compounds.
[0081] Furthermore, the free radical polymerizable liquid crystal compound contained in the liquid crystal composition can be any one of low molecular weight free radical polymerizable liquid crystal compounds and high molecular weight free radical polymerizable liquid crystal compounds, or a mixture thereof.
[0082] As a free radical polymerizable rod-shaped liquid crystal compound, the compound described in claim 1 of Japanese Patent Application Publication No. 11-513019 or in paragraphs
[0026] to
[0098] of Japanese Patent Application Publication No. 2005-289980 is preferred. As a free radical polymerizable disk-shaped liquid crystal compound, the compound described in paragraphs
[0020] to
[0067] of Japanese Patent Application Publication No. 2007-108732 or in paragraphs
[0013] to
[0108] of Japanese Patent Application Publication No. 2010-244038 is preferred.
[0083] As a free radical polymerizable liquid crystal compound, a free radical polymerizable liquid crystal compound with reverse wavelength dispersion (reverse dispersion compound) can be used. In this specification, a liquid crystal compound with "reverse wavelength dispersion" means that when the in-plane retardation (Re) value of a film made using this liquid crystal compound is measured at a specific wavelength (visible light range), the Re value increases to the same extent or increases with increasing measurement wavelength.
[0084] There are no particular limitations on free radical polymerizable liquid crystal compounds with reverse wavelength dispersion, as long as they can form a layer with reverse wavelength dispersion. For example, compounds represented by general formula (1) as described in Japanese Patent Application Publication No. 2010-084032 (especially the compounds described in paragraphs
[0067] to
[0073] ), compounds represented by general formula (1) as described in Japanese Patent Application Publication No. 2016-081035 (especially the compounds described in paragraphs
[0043] to
[0055] ), and compounds represented by general formula (II) as described in Japanese Patent Application Publication No. 2016-053709 (especially the compounds described in paragraphs
[0036] to
[0043] ).
[0085] Furthermore, examples of free radical polymerizable liquid crystal compounds with reverse wavelength dispersibility include paragraphs
[0027] to
[0100] of Japanese Patent Application Publication No. 2011-006360, paragraphs
[0028] to
[0125] of Japanese Patent Application Publication No. 2011-006361, paragraphs
[0016] to
[0345] of Japanese Patent Application Publication No. 2012-077055, and International Publication No. 201 The compounds described in paragraphs
[0017] to
[0072] of Publication No. 2 / 141245, paragraphs
[0021] to
[0088] of Publication No. 2012 / 147904, paragraphs
[0028] to
[0115] of Publication No. 2014 / 147904, and paragraphs
[0025] to
[0056] of Publication No. 2021 / 060427.
[0086] Free radical polymerizable liquid crystal compounds can be used alone or in combination of two or more.
[0087] The content of the free radical polymerizable liquid crystal compound is preferably 50 to 99.99% by mass relative to the total solid content of the liquid crystal composition, more preferably 70 to 99% by mass.
[0088] <Specific leveling agents>
[0089] The liquid crystal composition contains a specific leveling agent. The specific leveling agent has repeating units containing silicon atoms (hereinafter also referred to as "repeating unit A"), repeating units containing cationic polymerizable groups (hereinafter also referred to as "repeating unit B"), and repeating units containing free radical polymerizable groups (hereinafter also referred to as "repeating unit C").
[0090] (Repeating Unit A)
[0091] Repeating unit A is a repeating unit containing silicon atoms.
[0092] The number of silicon atoms contained in the repeating unit A is 1 or more, preferably 3 or more, more preferably 3 to 30, even more preferably 3 to 20, and especially preferably 3 to 15.
[0093] The repeating unit A is preferably a repeating unit containing a group represented by formula (Ia) (hereinafter also referred to as "repeating unit A1") or a repeating unit containing a group represented by formula (Ib) (hereinafter also referred to as "repeating unit A2").
[0094] Repeating Unit A1
[0095] The repeating unit A1 is a repeating unit containing a group represented by formula (Ia).
[0096] [Chemical Formula 1]
[0097] In equation (Ia), Indicates the bonding location.
[0098] R A Each can be independently represented as an alkyl, alkenyl, aryl, or aralkyl group that may have substituents. Preferred substituents are halogen atoms, alkyl, alkenyl, alkyl carbonyl, alkoxy carbonyl, alkyl carbonyloxy, or alkoxy groups.
[0099] Examples of alkyl groups include, for example, straight-chain alkyl groups with 1 to 18 carbon atoms and branched or cyclic alkyl groups with 3 to 18 carbon atoms. Specifically, examples include methyl, ethyl, propyl, butyl, isopropyl, tert-butyl, and cyclohexyl.
[0100] Examples of alkenyl groups with 2 to 12 carbon atoms can be cited as examples.
[0101] Examples of aryl groups with 6 to 12 carbon atoms can be cited as examples of the aforementioned aryl groups.
[0102] Examples of aralkyl groups with 7 to 30 carbon atoms can be cited as aralkyl groups.
[0103] From the perspective of superior leveling properties, R A Preferably, it is an alkyl group, more preferably a straight-chain alkyl group having 1 to 18 carbon atoms (preferably 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms).
[0104] In addition, there are multiple R A They can be the same as each other, or they can be different.
[0105] From the viewpoint of achieving better results from the present invention, the repeating unit A preferably contains two or more groups represented by formula (Ia), more preferably contains three to six such groups, and even more preferably contains three to five such groups.
[0106] From the viewpoint of superior leveling properties and compatibility with liquid crystal compounds, repeating unit A1 is preferably a repeating unit containing a group represented by the following formula (Ia-1).
[0107] [Chemical Formula 2]
[0108] In equation (Ia-1), R A R in equation (Ia) A The meanings are the same, and the preferred methods are also the same. Furthermore, there are multiple R... A They can be the same as each other, or they can be different.
[0109] In equation (Ia-1), L A This represents the m+1 valence linker.
[0110] Examples of chain-like (straight-chain or branched-chain) aliphatic hydrocarbon groups with an m+1 valence can be cited as the above-mentioned m+1 valence chain-like aliphatic hydrocarbon groups. However, in the above-mentioned chain-like aliphatic hydrocarbon groups with an m+1 valence, at least one -CH2- can be replaced by -NH-, -O-, -S-, -CO-, -SO- or -SO2-, at least one -CH2CH2- can be replaced by -N=N- or -CH=N-, at least one -CH< can be replaced by -N< or -SiH<, and at least one >C< can be replaced by >Si<.
[0111] The number of carbon atoms in the chain-like aliphatic hydrocarbon group with the above-mentioned m+1 valence is preferably 1 to 20, more preferably 1 to 15, and even more preferably 1 to 10.
[0112] The number of atoms other than hydrogen atoms in the chain-like aliphatic hydrocarbon group with the above-mentioned m+1 valence is preferably 1 to 20, more preferably 1 to 15, and even more preferably 1 to 10.
[0113] In addition, the aforementioned aliphatic hydrocarbon groups with an m+1 valence can further have substituents (e.g., halogen atoms and aryl groups).
[0114] As L A Examples include groups represented by the structural formulas K-1-L, K-2-L, K-3-L, and K-4-L. Additionally, in the following structural formulas, This indicates that -Si(R) in equation (Ia-1) A)3 indicates the bonding position of the group. L represents A Another bonding location. And, R in the following structural formula... T The meaning of R in equation (Ia-1) A The meanings are the same.
[0115] [Chemical Formula 3]
[0116] In formula (Ia-1), m represents 2 or 3, and from the viewpoint of achieving better results in this invention, 3 is preferred.
[0117] In equation (Ia-1), Indicates the bonding location.
[0118] From the viewpoint of superior leveling properties and compatibility with liquid crystal compounds, the repeating unit A1 is preferably a repeating unit represented by the following formula (a1).
[0119] [Chemical Formula 4]
[0120] In equation (a1), R A R in equation (Ia) A The meanings are the same, and the preferred methods are also the same. Furthermore, there are multiple R... A They can be the same as each other, or they can be different.
[0121] In equation (a1), L A and m and L in equation (Ia-1) A The meanings of 'm' and 'm' are the same, and the preferred selection methods are also the same.
[0122] In equation (a1), R 1 and R 2 Each can be used to represent a hydrogen atom or an alkyl group independently.
[0123] Examples of alkyl groups include, for example, straight-chain alkyl groups with 1 to 18 carbon atoms and branched or cyclic alkyl groups with 3 to 18 carbon atoms. Specifically, examples include methyl, ethyl, propyl, butyl, isopropyl, tert-butyl, and cyclohexyl.
[0124] As R 1 and R 2 Preferably, it contains hydrogen atoms.
[0125] In equation (a1), R 3 It represents a hydrogen atom or a substituent.
[0126] Examples of substituents include alkyl, alkenyl, aryl, or substituents having a linking group and a group containing a silicon atom. Substituents having a linking group and a group containing a silicon atom also include -CH2-CO-L. 1 -L A -(Si(R) A 3) m L 1 L A R A and m are respectively related to L in equation (a1) 1 L A R A The meanings of 'm' and 'm' are the same, and the preferred selection methods are also the same.
[0127] As R 3 Preferably, it is a hydrogen atom or an alkyl group, more preferably a hydrogen atom or a straight-chain alkyl group having 1 to 4 carbon atoms, and even more preferably a hydrogen atom, methyl or ethyl group, especially preferably a hydrogen atom or methyl group.
[0128] In equation (a1), L 1 Indicates -O- or -NR Z -. R Z It represents a hydrogen atom or a substituent.
[0129] As a result of R Z The substituents represented, for example, can be exemplified as those derived from R 3 The substituents represented are preferably alkyl groups, more preferably straight-chain alkyl groups having 1 to 4 carbon atoms, and even more preferably methyl or ethyl.
[0130] As L 1 Preferably -O- or -NH-, more preferably -O-.
[0131] Repeating Unit A2
[0132] The repeating unit A2 is a repeating unit containing a group represented by formula (Ib).
[0133] [Chemical Formula 5]
[0134] In equation (Ib), R B R in equation (Ia) A The meanings are the same, and the preferred methods are also the same. Furthermore, there are multiple R... B They can be the same as each other, or they can be different.
[0135] n is a repetition number, representing a number greater than 2. As a lower limit for n, from the viewpoint of better performance of the present invention, 6 or more is preferred. As an upper limit for n, 50 or less is preferred, more preferably 30 or less, and even more preferably 10 or less.
[0136] Indicates the bonding location.
[0137] From the viewpoint of superior leveling properties and compatibility with liquid crystal compounds, the repeating unit A2 is preferably a repeating unit represented by the following formula (a2).
[0138] [Chemical Formula 6]
[0139] In equation (a2), R B and n are respectively related to R in equation (Ib) B And n has the same meaning, and the optimal selection method is also the same. In addition, there are multiple R... B They can be the same as each other, or they can be different.
[0140] In equation (a2), R 1 R 2 R 3 and L 1 respectively with R in equation (a1) 1 R 2 R 3 and L 1 The meanings are the same, and the preferred selection methods are also the same.
[0141] In equation (a2), L B This indicates a divalent linker.
[0142] Examples of divalent linkers include chain-like (straight-chain or branched) alkylene groups. However, in these chain-like alkylene groups, at least one -CH2- may be replaced by -NH-, -O-, -S-, -CO-, -SO-, or -SO2-, and at least one -CH2CH2- may be replaced by -N=N-, -CH=N-, or -CR. S =CR S -(R) S Represents a hydrogen atom or a halogen atom. ) or -C≡C- substitution, at least one -CH< can be substituted by -N< or -SiH<, at least one >C< can be substituted by >Si<.
[0143] The number of carbon atoms in the above-mentioned chain-like alkylene groups is preferably 1 to 20, more preferably 1 to 15, and even more preferably 1 to 10.
[0144] The number of atoms other than hydrogen atoms in the aforementioned chain-like alkylene group is preferably 1 to 20, more preferably 1 to 15, and even more preferably 1 to 10.
[0145] In addition, the aforementioned chain-like alkylene groups may further have substituents (e.g., halogen atoms and aryl groups).
[0146] As a specific example of the aforementioned divalent linker, one can be a straight-chain alkylene group with at least one -CH2- that can be replaced by -NH-, -O-, -S-, -CO-, -SO- or -SO2- and has 1 to 12 carbon atoms (preferably 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms).
[0147] In equation (a2), R C This represents an organic group with a monovalent valence.
[0148] As a result of R C The monovalent organic group can be represented by, for example, alkyl, alkenyl, aryl or aralkyl groups that may have substituents, or groups represented by the above formula (Ia).
[0149] Examples of alkyl, alkenyl, aryl, and aralkyl groups that can have substituents include those corresponding to R in formula (Ia) above. A The same group as the group described.
[0150] The preferred substituents are halogen atoms, alkyl groups, alkenyl groups, alkyl carbonyl groups, alkoxy carbonyl groups, alkyl carbonyloxy groups, or alkoxy groups.
[0151] From the viewpoint that the present invention has superior effects, R C Preferably, it is an alkyl group or a group represented by the above formula (Ia), more preferably a straight-chain alkyl group or a group represented by the above formula (Ia) having 1 to 18 carbon atoms (preferably 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms).
[0152] As a specific example of repeating unit A, repeating units derived from the monomers represented by K-1 to K-33 below can be cited. Additionally, nBu represents n-butyl.
[0153] [Chemical Formula 7] [Chemical Formula 8]
[0154] Repeating unit A can be used alone or in combination with two or more types.
[0155] The content of repeating unit A relative to all repeating units of the specific leveling agent (all repeating units constituting the main chain of the specific leveling agent (100% by mass)) is preferably 20% by mass or more, more preferably 30% by mass or more, further preferably 40% by mass or more, and especially preferably 50% by mass or more. The upper limit of the content of repeating unit A relative to all repeating units constituting the main chain of the specific leveling agent (100% by mass) is preferably 90% by mass or less, more preferably 80% by mass or less, further preferably 70% by mass or less, and most preferably 60% by mass or less.
[0156] (Repeating Unit B)
[0157] Repeating unit B is a repeating unit containing a cationic polymerizable group.
[0158] As the cationic polymerizable group, known cationic polymerizable groups can be used, such as alicyclic ether groups, cyclic acetal groups, cyclic lactone groups, cyclic thioether groups, spirocyclic orthoester groups, and vinyloxy groups. Among these, alicyclic ether groups or vinyloxy groups are preferred, and epoxy groups, oxetyl groups, or vinyloxy groups are more preferred.
[0159] Furthermore, the epoxy group can be fused with a cyclic group (such as an alicyclic group). The cyclic group fused with the epoxy group preferably has 5 to 15 carbon atoms. Moreover, in the aforementioned cyclic group, the portion other than the fused epoxy group can be monocyclic or polycyclic. It is also preferable that the epoxy group does not fused with the cyclic group.
[0160] Furthermore, the oxetane group can be fused with a cyclic group (such as an alicyclic group). The cyclic group fused with the oxetane group preferably has 5 to 15 carbon atoms. Moreover, in the aforementioned cyclic group, the portion other than the fused oxetane group can be monocyclic or polycyclic. The oxetane group is also preferably not fused with the cyclic group.
[0161] In repeating unit B, from the viewpoint of achieving better results in this invention, it is preferable that the length (hereinafter also referred to as "length Ak") from the main chain to the cationic polymeric group is 8 atoms or more.
[0162] If we take the following compound having a cationic polymerizable group (epoxy group) as an example, then The length (Ak) from the main chain to the cationic polymeric group is 8. That is, in the following compounds, the length Ak refers to the length of the connecting portion between the main chain and the cationic polymeric group at the end.
[0163] [Chemical Formula 9]
[0164] Furthermore, although not illustrated, examples include compounds having cationic polymerizable groups that are acyclic groups. If we take the vinyloxy group as an example of a non-cyclic cationic polymerizable group, then the length of the oxygen atom contained in the vinyloxy group from the main chain to the length Ak is called the length.
[0165] However, when the repeating unit B has multiple cationic polymerizable groups, the longest of the lengths from the main chain to the cationic polymerizable groups is taken as the aforementioned length Ak.
[0166] From the viewpoint of achieving better results with this invention, the length Ak is preferably 8 atoms or more, more preferably 10 atoms or more. Furthermore, as an upper limit, it is preferably 20 atoms or less.
[0167] From the viewpoint of superior compatibility with liquid crystal compounds, the repeating unit B is preferably a repeating unit represented by the following formula (b1).
[0168] [Chemical Formula 10]
[0169] In equation (b1), R 21 R 22 R 23 and L 1 respectively with R in the above formula (a1) 1 R 2 R 3 and L 1 The meanings are the same, and the preferred selection methods are also the same.
[0170] In equation (b1), L 3 This indicates a single bond or a divalent linker.
[0171] Examples of divalent linking groups include divalent aliphatic hydrocarbon groups with 1 to 20 carbon atoms that can have substituents.
[0172] The aliphatic hydrocarbon group having 1 to 20 carbon atoms is preferably an alkylene group having 1 to 15 carbon atoms, and more preferably an alkylene group having 2 to 8 carbon atoms.
[0173] One or more of the -CH2- groups constituting the divalent aliphatic hydrocarbon group described above can be independently substituted by groups selected from -O-, -S-, -CO-, and -N(Q)-. Furthermore, two or more -CH2- groups can be substituted, provided that the same groups are not adjacent. Q represents a hydrogen atom or a substituent. The substituent represented by Q is preferably an alkyl group, more preferably a straight-chain alkyl group having 1 to 4 carbon atoms, and even more preferably methyl or ethyl.
[0174] As L 3 Preferably, the alkylene group having 2 to 8 carbon atoms may have a substituent. -(L31 -O) n3 - . Indicates the bonding position. n3 represents an integer from 1 to 8. L 31 Each of the following can be independently represented as an alkylene group having 1 to 6 carbon atoms that may have substituents, preferably an alkylene group having 2 to 4 carbon atoms that may have substituents.
[0175] Examples of substituents that can be present as the aforementioned divalent linker include hydroxyl, halogen, amino, alkyl, alkoxy, acyl, aryl, nitro, cyano, alkyl carbonyl, and sulfonyl groups.
[0176] In equation (b1), P 1 This indicates a cationic polymerizable group. The definition and preferred method of cationic polymerizable groups are as described above.
[0177] Furthermore, in the repeating unit represented by formula (b1), the length (length Ak) from the main chain to the cationic polymeric group is preferably 8 atoms or more.
[0178] As a specific example of repeating unit B, repeating units R-1 to R-11 can be given as follows.
[0179] [Chemical Formula 11]
[0180] Repeating unit B can be used alone or in combination with two or more types.
[0181] The content of repeating unit B is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, relative to all repeating units (100% by mass) constituting the main chain of the specific leveling agent. The upper limit of the content of repeating unit B is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 15% by mass or less, relative to all repeating units (100% by mass) constituting the main chain of the specific leveling agent.
[0182] (Repeating Unit C)
[0183] The repeating unit C is a repeating unit containing a free radical polymerizable group.
[0184] As a free radical polymerizable group, for example, known free radical polymerizable groups having unsaturated double bond groups can be cited. Specific examples of free radical polymerizable groups include vinyl, allyl, vinyloxy, maleimide, allyloxy, (meth)acryloyl, (meth)acryloyloxy, and (meth)acrylamido, among which (meth)acryloyl or (meth)acryloyloxy is preferred.
[0185] In the repeating unit C, the number of free radical polymerizable groups is 1 or more, preferably 1 to 3, and more preferably 1 or 2.
[0186] In the repeating unit C, from the viewpoint of achieving better results in this invention, it is preferable that the aforementioned free radical polymerizable group is a free radical polymerizable group having an unsaturated double bond group, and the length (hereinafter also referred to as "length Ar") from the main chain to the unsaturated double bond group contained in the aforementioned free radical polymerizable group is 7 atoms or more.
[0187] Taking the following compound as an example, the length (length Ar) from the main chain to the unsaturated double bond group of the free radical polymerizable group is 8. That is, the length Ar in the following compound refers to the length of the connecting portion of the unsaturated double bond group contained in the free radical polymerizable group that connects the main chain and the end of the free radical polymerizable group.
[0188] [Chemical Formula 12]
[0189] However, when the repeating unit C has multiple free radical polymerizable groups, the longest of the lengths from the main chain to the free radical polymerizable groups is taken as the aforementioned length Ar.
[0190] From the viewpoint of achieving better results with the present invention, the length Ar is preferably 7 atoms or more, more preferably 8 atoms or more, and even more preferably 10 atoms or more. Furthermore, as an upper limit, it is preferably 20 atoms or less.
[0191] From the viewpoint of achieving better results in this invention, the repeating unit B is preferably a repeating unit represented by formula (Z-1).
[0192] [Chemical Formula 13]
[0193] In equation (Z-1), D 1 Represents hydrogen atom, methyl group, -CH2OR Z1 or -CH2COOR Z2 R Z1 R represents an alkyl group having 1 to 4 hydrogen atoms or carbon atoms. Z2 It represents a hydrogen atom or a methyl group.
[0194] D 1 Preferably, it represents a hydrogen atom or a methyl group.
[0195] A 1 Indicates -O- or -NR Z3 -. R Z3 It represents an alkyl group having 1 to 4 hydrogen atoms or carbon atoms.
[0196] As R Z3Preferably, it is a hydrogen atom or a methyl group, more preferably a hydrogen atom.
[0197] As A 1 Preferably -O- or -NH-, more preferably -O-.
[0198] w represents an integer from 1 to 5.
[0199] From the viewpoint of achieving better results in this invention, w is preferably an integer from 2 to 5, more preferably 2 or 3, and even more preferably 2.
[0200] L Z1 It indicates a w+1 valence linker having at least one of the groups selected from aliphatic and aromatic groups.
[0201] The aforementioned aliphatic groups can be either chain-like (linear or branched) or cyclic. However, in the aliphatic group, at least one -CH2- can be replaced by -NR. Z4 -, -O-, -S-, -CO-, -SO- or -SO2- can be substituted, at least one -CH2CH2- can be substituted by -N=N- or -CH=N-, and at least one -CH< can be substituted by -N<.
[0202] R Z4 Indicates an alkyl group having 1 to 4 hydrogen atoms or carbon atoms. As R Z4 Preferably, it is a hydrogen atom or a methyl group, more preferably a hydrogen atom.
[0203] The aromatic group described above is preferably an aromatic hydrocarbon group, and more preferably an aromatic hydrocarbon group having 6 to 10 carbon atoms.
[0204] As the aforementioned w+1 valence linker, a chain-like (straight-chain or branched-chain) aliphatic hydrocarbon group with a w+1 valence is preferred, for example. However, in the aforementioned chain-like aliphatic hydrocarbon group with a w+1 valence, at least one -CH2- can be replaced by -NR. Z4 -, -O-, -S-, -CO-, -SO-, or -SO2- can be substituted; at least one -CH2CH2- can be substituted by -N=N- or -CH=N-; at least one -CH< can be substituted by -N<. Additionally, R Z4 As stated above.
[0205] The number of carbon atoms in the above-mentioned chain-like aliphatic hydrocarbon group with a w+1 valence is preferably 1 to 15, more preferably 1 to 10, even more preferably 1 to 6, and especially preferably 1 to 3.
[0206] The number of atoms other than hydrogen atoms in the above-mentioned w+1 valence chain aliphatic hydrocarbon group is preferably 1 to 15, more preferably 1 to 10, even more preferably 1 to 6, and particularly preferably 1 to 3.
[0207] In addition, the aforementioned aliphatic hydrocarbon groups with a w+1 valence can further have substituents (e.g., hydroxyl, halogen atom, and aryl group).
[0208] In the formula, when there are multiple R Z4 In the case of multiple R Z4 They can be the same as each other, or they can be different.
[0209] L Z2 Indicates a single bond or a bond selected from alkylene, arylene, -CO-, -O-, and -NR. Z5 - At least one of the divalent linkers in the group.
[0210] The aforementioned alkylene group is preferably in the form of a chain (straight chain or branched chain). Furthermore, the number of carbon atoms in the aforementioned alkylene group is preferably 1 to 10, more preferably 1 to 5, and even more preferably 1 to 3.
[0211] The aryl group is preferably an aryl group with 6 to 10 carbon atoms.
[0212] R Z5 The alkyl group represents 1 to 4 carbon atoms, preferably hydrogen atoms or methyl groups, and more preferably hydrogen atoms.
[0213] In the formula, when there are multiple R Z5 In the case of multiple R Z5 They can be the same as each other, or they can be different.
[0214] Among them, L Z2 Preferably, it is a single bond or has a bond selected from alkylene, -CO-, -O-, and -NR. Z5 - at least one of the divalent linkers in the group consisting of -, more preferably a single bond or having at least one divalent linker selected from the group consisting of alkylene, -CO- and -O-, and even more preferably a single bond or alkylene.
[0215] In the formula, when there are multiple L Z2 In the case of multiple L Z2 They can be the same as each other, or they can be different.
[0216] From the perspective of improving scratch resistance, L in equation (Z-1) Z1 and w L Z2 The part that constitutes (in formula (Z-1) is composed of (-L) Z1 -(L Z2 ) w The portion indicated by - preferably does not contain heteroatoms. Furthermore, as L in formula (Z-1) Z1 and w L Z2 The number of carbon atoms contained in the constituent part is preferably 1 to 6, more preferably 1 to 5, even more preferably 1 to 4, and especially preferably 1 to 3.
[0217] E 1 It indicates a free radical polymerizable group.
[0218] As a result of E 1 The free radical polymerizable group represented can be any of the free radical polymerizable groups already described. Preferably, it is a group represented by formula (Ea-1) or a group represented by formula (Ea-2), and more preferably a group represented by formula (Ea-1).
[0219] In the formula, when there are multiple E 1 In the case of multiple E 1 They can be the same as each other, or they can be different.
[0220] [Chemical Formula 14]
[0221] In equation (Ea-1), R E1 Each can be used to represent a hydrogen atom or a methyl group independently.
[0222] In equation (Ea-2), R E2 Each can be used independently to represent a hydrogen atom or a methyl group. R E3 The alkyl group represents 1 to 4 carbon atoms, preferably hydrogen atoms or methyl groups, and more preferably hydrogen atoms.
[0223] In equations (Ea-1) and (Ea-2), Indicates the bonding location.
[0224] Furthermore, in the repeating unit represented by formula (Z-1), the length (length Ar) of the unsaturated double bond group contained in the free radical polymerizable group represented by formulas (Ea-1) and (Ea-2) from the main chain is preferably 7 atoms or more, more preferably 8 atoms or more, and even more preferably 10 atoms or more. In addition, as an upper limit, it is preferably 20 atoms or less.
[0225] As a specific example of a repeating unit C, repeating units represented by H-1 to H-20 below can be given. n represents the number of repetitions, which is an integer from 1 to 100.
[0226] [Chemical Formula 15] [Chemical Formula 16] [Chemical Formula 17]
[0227] The repeating unit C can be used alone or in combination of two or more types.
[0228] The content of repeating unit C is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, relative to all repeating units (100% by mass) constituting the main chain of the specific leveling agent. The upper limit of the content of repeating unit C is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 15% by mass or less, relative to all repeating units (100% by mass) constituting the main chain of the specific leveling agent.
[0229] A certain leveling agent may have repeating units other than the repeating units A to C mentioned above.
[0230] From the viewpoint of orientation control of the free radical polymerizable liquid crystal compound described above, a particular leveling agent is also preferably having repeating units (repeating units D) containing mesocrystalline groups.
[0231] (Repeating unit D)
[0232] The repeating unit D is a repeating unit containing a mesocrystalline group.
[0233] As the aforementioned mesocrystalline base, a known mesocrystalline base can be used, for example, as described in "Flussige Kristallein Tabellen II" (VEB Deutsche Verlag fur Grundstoff Industrie, Leipzig, 1984), especially pages 7 to 16, and as described in the LCD Handbook Editorial Committee, LCD Handbook (Maruzen, 2000), especially Chapter 3.
[0234] As a mesocrystalline group, it is preferably a group having at least one cyclic structure selected from the group consisting of aromatic hydrocarbon groups, heterocyclic groups and alicyclic groups.
[0235] From the viewpoint of improving the orientation degree of liquid crystal compounds, and considering the reasons for improving the orientation degree of liquid crystal compounds, the mesocrystalline group is preferably a group that can have substituents, has aromatic hydrocarbon groups, or has alicyclic groups; more preferably, it is a group that can have substituents and has 2 to 4 aromatic hydrocarbon groups; and even more preferably, it is a group that can have substituents and has 3 aromatic hydrocarbon groups. As substituents, alkyl, alkoxy, alkyl ester, or acetyl groups are preferred, and methyl, tert-butyl, methoxy, or methyl ester groups are more preferred.
[0236] As a mesocrystalline group, it is preferably a group represented by the following formula (M1-A). -(Cy 11 -L 11 ) n -Cy 12 - (M1-A)
[0237] In formula (M1-A), Indicates the bonding location.
[0238] In formula (M1-A), n represents an integer greater than or equal to 1, preferably an integer from 1 to 10, more preferably an integer from 1 to 3, and even more preferably 2.
[0239] In formula (M1-A), Cy 11 and Cy 12 Each can be independently represented as a divalent cyclogroup that may have substituents.
[0240] The divalent cyclic group mentioned above can be either monocyclic or polycyclic, preferably monocyclic.
[0241] The number of ring elements in the divalent ring base is preferably 5 to 18, more preferably 5 to 10, and even more preferably 5 or 6.
[0242] Examples of divalent cyclic groups include divalent aromatic cyclic groups and divalent alicyclic groups.
[0243] Examples of divalent aromatic cyclic groups include divalent aromatic hydrocarbon cyclic groups obtained by removing two hydrogen atoms from an aromatic hydrocarbon ring and divalent aromatic heterocyclic groups obtained by removing two hydrogen atoms from an aromatic heterocycle. Examples of aromatic hydrocarbon rings include benzene rings, naphthyl rings, anthracene rings, and phenanthroline rings. Examples of aromatic heterocycles include pyridine rings, pyridazine rings, imidazole rings, thiophene rings, quinoline rings, isoquinoline rings, oxazole rings, thiazole rings, oxadiazole rings, benzothiazole rings, benzothiazole rings, phthalimide rings, thienothiazole rings, thiazolenothiazole rings, thienothiphene rings, and thienooxazole rings. Among these, groups obtained by removing two hydrogen atoms from a benzene ring (e.g., 1,4-phenylene) are preferred.
[0244] Examples of divalent alicyclic groups include divalent alicyclic groups obtained by removing two hydrogen atoms from an aliphatic hydrocarbon ring (e.g., cycloalkanes and cycloalkenes) and divalent aliphatic heterocyclic groups obtained by removing two hydrogen atoms from an aliphatic heterocycle. Examples of aliphatic hydrocarbon rings include cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclododecane, and cyclodocosahexadecane. Examples of aliphatic heterocycles include pyrrolidine, oxetane, thiophene, piperidine, tetrahydropyran, thiaran, piperazine, and morpholine rings. Among these, groups obtained by removing a divalent hydrogen atom from a cyclohexane ring (e.g., 1,4-cyclohexene) are preferred.
[0245] The divalent cyclogroup is preferably a divalent aromatic cyclogroup or a divalent aliphatic hydrocarbon cyclogroup, and more preferably a divalent aromatic cyclogroup.
[0246] Substituents that can be present as the divalent cyclogroups mentioned above include, for example, alkyl groups, alkyl groups, acyl groups, alkoxy groups, alkoxythio groups, alkoxycarbonyl groups, carbamoyl groups, amide groups, halogen groups, cyano groups, and nitro groups, preferably alkyl groups, alkyl groups, or acyl groups, more preferably methyl groups, straight-chain alkyl groups or acetyl groups having 1 to 4 carbon atoms, and even more preferably methyl groups, methyl groups, or ethyl groups.
[0247] In formula (M1-A), L 11 Each can be used to independently represent a single bond or a divalent linker.
[0248] Examples of divalent linkers include -CO-, -O-, -S-, -C(=S)-, and -CR. L1 R L2 -、-CR L3 =CR L4 -and-NR L5 -And combinations of two or more of these. R L1 ~R L5 Each can be used independently to represent a hydrogen atom or a substituent. As a group consisting of R... L1 ~R L5 The substituents indicated are preferably halogen atoms, alkyl groups having 1 to 12 carbon atoms, or alkoxy groups having 1 to 12 carbon atoms.
[0249] As L 11 Preferably -CO-, -O-, or -CR L1 R L2 -、-NR L5 - Or a combination of these two.
[0250] When n is an integer greater than 2 and Cy 11 When representing phenylene, from the viewpoint of improving orientation when aligning liquid crystal compounds horizontally, two or more Cy atoms are used. 11 Any one of them is preferably interpositional or adjacent connection, wherein, from the viewpoint of improving orientation and reducing pinhole defects, interpositional connection is preferred. On the other hand, when vertically aligning the liquid crystal compound, two or more Cy 11 Either of them is preferably a positional connection.
[0251] From the viewpoint of improving compatibility with liquid crystal compounds and achieving better leveling properties, the repeating unit D is preferably a repeating unit represented by the following formula (d1) or a repeating unit represented by formula (d2), and more preferably a repeating unit represented by formula (d1).
[0252] [Chemical Formula 18]
[0253] In equations (d1) and (d2), R21 R 22 R 23 and L 1 respectively with R in the above formula (a1) 1 R 2 R 3 and L 1 The meanings are the same, and the preferred selection methods are also the same.
[0254] In the above formula (d2), R 24 and R 25 respectively with R in the above formula (a1) 1 and R 2 The meanings are the same, and the selection methods are also the same. R 26 R in the above formula (a1) 3 The meanings are the same, and the selection methods are also the same. L 2 L in the above formula (a1) 1 The meanings are the same, and the preferred selection methods are also the same.
[0255] In equations (d1) and (d2), SP 1 and SP 2 Each of the spacer bases can be represented independently.
[0256] There are no particular restrictions as long as the spacer group is a divalent linker that does not contain a ring structure. For example, divalent chain aliphatic hydrocarbon groups with 1 to 20 carbon atoms can be cited.
[0257] The preferred form of the divalent aliphatic hydrocarbon group having 1 to 20 carbon atoms is a chain-like alkylene group having 1 to 15 carbon atoms, and more preferably a chain-like alkylene group having 1 to 8 carbon atoms. Specifically, suitable examples include methylene, ethylene, propylene, butylene, pentylene, hexylene, methylhexylene, and heptylene.
[0258] One or more of the -CH2- groups constituting the divalent chain aliphatic hydrocarbon group described above can be independently substituted by groups selected from -O-, -S-, -CO-, and -N(Q)-. Furthermore, two or more -CH2- groups can be substituted as long as the same groups are not adjacent. Q represents a hydrogen atom or a substituent. The substituent represented by Q is preferably an alkyl group, more preferably a straight-chain alkyl group having 1 to 4 carbon atoms, and even more preferably methyl or ethyl.
[0259] As the aforementioned spacer base, preferably, -(CH2-CH2-O) n1 - , -(CH2) n2 -O- or -(CH2)n2 -O-CO- . Indicates the bonding position. n1 represents an integer from 1 to 4. n2 independently represents an integer from 1 to 6, preferably an integer from 2 to 4.
[0260] In equations (d1) and (d2), M 1 This indicates a mesocrystalline group. Details about mesocrystalline groups are as described above.
[0261] In equation (d2), T 1 This indicates a terminal group. A terminal group can represent a hydrogen atom or a substituent.
[0262] Examples of substituents mentioned above include halogen atoms, cyano groups, nitro groups, hydroxyl groups, alkyl groups with 1 to 10 carbon atoms, alkoxy groups with 1 to 10 carbon atoms, alkylthio groups with 1 to 10 carbon atoms, alkoxycarbonyloxy groups with 1 to 10 carbon atoms, alkoxycarbonyl groups with 1 to 10 carbon atoms (ROC(O)-: R is alkyl), acyloxy groups with 1 to 10 carbon atoms, amide groups with 1 to 10 carbon atoms, alkoxycarbonylamino groups with 1 to 10 carbon atoms, sulfonamide groups with 1 to 10 carbon atoms, aminosulfonyl groups with 1 to 10 carbon atoms, carbamoyl groups with 1 to 10 carbon atoms, sulfinyl groups with 1 to 10 carbon atoms, trialkylsilyloxy groups with 3 to 12 carbon atoms, and urea groups with 1 to 10 carbon atoms.
[0263] As a specific example of the repeating unit D, for example, repeating units derived from the monomers represented by Q-1 to Q-32 below can be cited.
[0264] [Chemical Formula 19] [Chemical Formula 20]
[0265] The repeating unit D can be used alone or in combination of two or more types.
[0266] The content of repeating unit D is preferably 5 to 50% by mass relative to all repeating units (100% by mass) of the main chain constituting the specific leveling agent, more preferably 10 to 50% by mass, and even more preferably 15 to 45% by mass.
[0267] The total content of the aforementioned repeating units A, B, and C is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, relative to all repeating units in the main chain constituting the specific leveling agent. There is no particular upper limit, and it can be 100% by mass.
[0268] The total content of the aforementioned repeating units A, B, C, and D is preferably 80% by mass or more, more preferably 90% by mass or more, relative to all repeating units in the main chain constituting the specific leveling agent. There is no particular upper limit, and it can be 100% by mass.
[0269] (Other repeating units)
[0270] A particular leveling agent may contain repeating units other than those described above.
[0271] For example, from the viewpoint of orientation control, a particular leveling agent may have repeating units containing polar groups. Examples of polar groups include carboxyl, amino, amide, urea, carbamate, sulfonamide, sulfonyl, phosphate, hydroxyl, mercapto, methylene substituted with an electron-withdrawing group, and methine substituted with an electron-withdrawing group, with carboxyl being preferred.
[0272] As a repeating unit containing a polar group, it is preferred to be a repeating unit represented by the following formula (K-1).
[0273] [Chemical Formula 21]
[0274] In the above formula (K-1), R 10 The alkyl group represents 1 to 20 hydrogen atoms or carbon atoms, wherein preferably it is an alkyl group with 1 to 10 hydrogen atoms or carbon atoms, more preferably it is an alkyl group with 1 to 4 hydrogen atoms or carbon atoms, and even more preferably it is a hydrogen atom or a methyl group.
[0275] Examples of monomers that form repeating units represented by the above formula (K-1) include acrylic acid and methacrylic acid.
[0276] The content of repeating units with polar groups is preferably 0.05 to 30% by mass relative to all repeating units (100% by mass) constituting the main chain of a particular leveling agent, more preferably 0.1 to 15% by mass, and even more preferably 1 to 10% by mass.
[0277] Furthermore, as repeating units other than those mentioned above, examples include repeating units derived from alkyl methacrylates (the alkyl portion has 1 to 24 carbon atoms), styrene derivatives, (meth)acrylonitrile, vinyl ether derivatives, and alkyl (meth)acrylamide derivatives, as well as repeating units having functional groups capable of forming covalent complexes with hydroxyl groups.
[0278] As functional groups capable of forming covalently bonded complexes with hydroxyl groups, borate groups (-B(OH)2) and borate ester groups (-B(OR)2) are preferred. B1 )2) Base. R B1This represents a monovalent organic group. Furthermore, the two R groups... B1 They can bond together to form a ring structure.
[0279] As a repeating unit having a functional group capable of forming a covalently bonded complex with a hydroxyl group, examples of repeating units can be given, for instance, as shown below.
[0280] [Chemical Formula 22]
[0281] As a repeating unit containing a borate group or a borate ester group, for example, the repeating unit described in paragraphs 0036 to 0045 of International Publication No. 2018 / 062068 can also be cited.
[0282] The specific leveling agent can be any of the random copolymers, alternating copolymers, and block copolymers. Furthermore, random, alternating, and block copolymers can also coexist in a mixture.
[0283] The weight-average molecular weight of the specific leveling agent is preferably 5,000 to 70,000, more preferably 9,000 to 40,000, and even more preferably 15,000 to 30,000.
[0284] Here, the weight-average molecular weight in this invention is the value determined by gel permeation chromatography (GPC) under the following conditions. • Solvent (eluent): Tetrahydrofuran • Device Name: EcoSEC HLC-8320GPC (Manufactured by TOSOH CORPORATION) • Chromatographic columns: Connect three chromatographic columns: TSKgel SuperHZM-H, TSKgel SuperHZ4000, and TSKgel SuperHZ200 (all manufactured by TOSOH CORPORATION). • Column temperature: 40℃ • Sample concentration: 0.1% by mass • Flow rate: 0.35 ml / min • Calibration curves: Calibration curves using six samples of TSK standard polystyrene manufactured based on TOSOH CORPORATION, with Mw=706000~1013 (Mw / Mn=1.03~1.06).
[0285] A specific leveling agent can be used alone or in combination of two or more.
[0286] From the viewpoint of achieving better results with the present invention, the content of the specific leveling agent relative to the total solid content of the liquid crystal composition is preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.1% by mass or less. Furthermore, from the viewpoint of leveling properties, the content of the specific leveling agent relative to the total solid content of the liquid crystal composition is preferably 0.001% by mass or more, more preferably 0.01% by mass or more.
[0287] <Polymerization Initiator>
[0288] The liquid crystal composition preferably contains a polymerization initiator.
[0289] There are no particular restrictions on the type of polymerization initiator, but photopolymerization initiator is preferred.
[0290] As photopolymerization initiators, known photopolymerization initiators can be used. Examples include α-carbonyl compounds, azo dye ethers, α-hydrocarbon-substituted aromatic azo dye compounds, polynuclear quinone compounds, combinations of triarylimidazolium dimers and p-aminophenyl ketones, acridine and phenazine compounds, oxadiazole compounds, O-acyl oxime compounds, and acylphosphine oxide compounds.
[0291] Commercially available products can also be used as photopolymerization initiators, such as Irgacure-184, Irgacure-907, Irgacure-369, Irgacure-651, Irgacure-819, Irgacure-OXE-01, and Irgacure-OXE-02 manufactured by BASF.
[0292] The content of the polymerization initiator is preferably 0.01 to 10% by mass relative to the total solid content of the liquid crystal composition, more preferably 0.1 to 5% by mass.
[0293] <Orientation Control Agent>
[0294] Liquid crystal compositions may include orientation control agents as needed.
[0295] Orientation control agents can be used to form various orientation states, including vertical orientation, tilted orientation, mixed orientation, and cholesterol-type orientation, in addition to homogeneous orientation. They can also control and achieve specific orientation states more uniformly and precisely.
[0296] As orientation control agents that promote homogeneous orientation, both low-molecular-weight and high-molecular-weight orientation control agents can be used.
[0297] As a low-molecular-weight orientation control agent, reference can be made to paragraphs
[0009] to
[0083] of Japanese Patent Application Publication No. 2002-020363, paragraphs
[0111] to
[0120] of Japanese Patent Application Publication No. 2006-106662, and paragraphs
[0021] to
[0029] of Japanese Patent Application Publication No. 2012-211306, the contents of which are incorporated herein by reference.
[0298] As an orientation control agent for polymers, reference can be made to paragraphs
[0021] to
[0057] of Japanese Patent Application Publication No. 2004-198511 and paragraphs
[0121] to
[0167] of Japanese Patent Application Publication No. 2006-106662, the contents of which are incorporated herein by reference.
[0299] Orientation control agents that form or promote vertical orientation include, for example, boric acid compounds and onium salt compounds. Specifically, reference can be made to the compounds described in Japanese Patent Application Publication No. 2008-225281, paragraphs
[0023] to
[0032] , Japanese Patent Application Publication No. 2012-208397, paragraphs
[0052] to
[0058] , Japanese Patent Application Publication No. 2008-026730, paragraphs
[0024] to
[0055] , and Japanese Patent Application Publication No. 2016-193869, paragraphs
[0043] to
[0055] , the contents of which are incorporated herein by reference.
[0300] Cholesterol-type orientation can be achieved by adding a chiral reagent to the liquid crystal composition, and the rotational direction of the cholesterol-type orientation can be controlled according to its chiral direction. Furthermore, the pitch of the cholesterol-type orientation can be controlled according to the orientation control force of the chiral reagent.
[0301] <Solvent>
[0302] From the viewpoint of workability of film formation, liquid crystal compositions preferably contain a solvent.
[0303] Examples of solvents include ketones (e.g., acetone, 2-butanone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone), ethers (e.g., dioxane, tetrahydrofuran, tetrahydropyran, dioxolane, tetrahydrofurfuryl alcohol, and cyclopentylmethyl ether), aliphatic hydrocarbons (e.g., hexane), alicyclic hydrocarbons (e.g., cyclohexane), aromatic hydrocarbons (e.g., benzene, toluene, xylene, and trimethylbenzene), carbon halogens (e.g., dichloromethane, chloroform, dichloroethane, dichlorobenzene, and chlorotoluene), and esters (e.g., ethyl acetate). Organic solvents such as methyl esters, ethyl acetate, ethyl propionate, butyl acetate and diethyl carbonate, alcohols (e.g. ethanol, isopropanol, butanol and cyclohexanol), cellosols (e.g. methyl cellosol, ethyl cellosol and 1,2-dimethoxyethane), cellosol acetates, sulfoxides (e.g. dimethyl sulfoxide), amides (e.g. dimethylformamide, dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone and 1,3-dimethyl-2-imidazolium ketone), and heterocyclic compounds (e.g. pyridine, etc.) as well as water.
[0304] These solvents can be used alone or in combination of two or more.
[0305] <Other Ingredients>
[0306] The liquid crystal composition may contain other components besides those mentioned above, as needed.
[0307] Other components include, for example, chiral agents, chain transfer agents, tilt angle control agents, plasticizers, and crosslinking agents.
[0308] From the viewpoint of uniformity and orientation, the liquid crystal composition is also preferably free of fillers (e.g., silicon dioxide).
[0309] [Manufacturing method of phase retardation film]
[0310] The phase retardation film of the present invention is formed using the above-described liquid crystal composition.
[0311] The method for manufacturing the phase retardation film of the present invention preferably includes, in sequence: a coating forming step of coating the above-mentioned liquid crystal composition to form a coating film; an alignment step of aligning the liquid crystal compound contained in the above-mentioned coating film; and an alignment fixing step of fixing the alignment state.
[0312] In the above-described coating formation process, a liquid crystal composition is coated onto a substrate to form a coating film. The substrate is not particularly limited; examples include the support and alignment film included in the optical laminate described later. By using a liquid crystal composition containing the aforementioned solvent, or by using a substance obtained by heating or otherwise molten the liquid crystal composition, it is easy to coat the alignment film with the liquid crystal composition.
[0313] Examples of coating methods for liquid crystal compositions include: roller coating, gravure printing, spin coating, wire rod coating, extrusion coating, direct gravure coating, reverse gravure coating, die coating, spray coating, and inkjet coating, among other known methods.
[0314] In the above-described alignment process, there are no particular limitations on the method for aligning the liquid crystal compound, but heat treatment is preferred. From the perspective of manufacturing suitability, the heating temperature is preferably 10–250°C, more preferably 25–190°C. Furthermore, the heating time is preferably 1–300 seconds, more preferably 1–60 seconds.
[0315] A cooling process can be performed after the above-described heat treatment. The cooling process involves cooling the heated coating film to approximately room temperature (20–25°C). There are no particular limitations on the cooling method, and it can be carried out using known methods.
[0316] The immobilization method in the above-mentioned orientation fixation process is typically a polymerization treatment (free radical polymerization treatment). Through free radical polymerization treatment, the orientation of the liquid crystal compound can be immobilized by polymerizing the free radical polymerizable liquid crystal compound and the free radical polymerizable groups contained in a specific leveling agent.
[0317] The conditions for the above polymerization are not particularly limited, but in light-based polymerization, ultraviolet light is typically preferred. The preferred irradiation dose is 10 mJ / cm². 2 ~50J / cm 2 More preferably 20 mJ / cm 2 ~5J / cm 2 Further preferred is 30 mJ / cm 2 ~3J / cm 2 The preferred value is 50–1000 mJ / cm³. 2 Furthermore, to promote the polymerization reaction, it can be carried out under heating conditions.
[0318] The method for manufacturing the retardation film of the present invention preferably includes a step of performing a surface modification treatment. Specifically, examples of the surface modification treatment include corona treatment and plasma treatment, with corona treatment being preferred. In other words, the retardation film is preferably subjected to corona treatment.
[0319] There are no particular restrictions on the timing of surface modification treatment, but it is preferred to perform it after the orientation fixing process.
[0320] The surface modification treatment described above is preferably applied to the surface of the coating film opposite to the substrate. In other words, it is preferably applied to the surface on the side where the specific leveling agent is located.
[0321] There are no particular limitations on the methods of corona treatment and plasma treatment; known methods can be used, such as well-known corona discharge devices and plasma treatment devices.
[0322] The discharge rate during corona treatment can be adjusted appropriately based on factors such as the composition of the phase retardation film, but is preferably 10 W / min / m. 2 The above is preferred, with 50 Wmin / m 2 The above is preferred, with 500 Wmin / m 2 That's all. There's no specific upper limit, but it's mostly around 5000 Wmin / m. 2 The preferred value is 2000 Wmin / m 2 the following.
[0323] The output and processing time in corona treatment can be adjusted appropriately.
[0324] [Properties of the phase difference film]
[0325] The phase retardation film of the present invention is a film in which the orientation state of the liquid crystal compound is immobilized by performing free radical polymerization treatment on the above-mentioned liquid crystal composition. The phase retardation film of the present invention typically comprises a cured product of a free radical polymerizable liquid crystal compound and a cured product of a specific leveling agent, wherein the orientation state of the liquid crystal compound is immobilized in order to exhibit the desired phase retardation function. In the above-mentioned phase retardation film, the cured product of the specific leveling agent is present biased on the surface of the phase retardation film and has cationic polymerizable groups derived from the specific leveling agent that have not participated in the free radical polymerization reaction.
[0326] Furthermore, in this specification, the term "fixed" orientation state of the liquid crystal compound refers to a state in which the orientation of the liquid crystal compound is maintained. Specifically, it is generally more preferable to maintain a fixed orientation state within a temperature range of 0–50°C, or more severely under conditions of -30–70°C, where there is no fluidity in the layer and the orientation morphology does not change due to external fields or forces. In a phase reversal film where the orientation state is fixed, the liquid crystal compound may no longer exhibit liquid crystal properties.
[0327] The orientation state of the liquid crystal compound in the phase retardation film of the present invention can be any of the following states: horizontal orientation, vertical orientation, tilted orientation, and twisted orientation.
[0328] Furthermore, as described in International Publication No. 2021 / 033640, the liquid crystal curing layer has, in the thickness direction, a first region formed by fixing the orientation state of a liquid crystal compound that is twisted along a helical axis extending in the thickness direction; and a second region formed by fixing the orientation state of a homogeneously oriented liquid crystal compound; and may also have multiple orientation states in one layer.
[0329] Furthermore, in this specification, "horizontal alignment" means that the main surface of the film is parallel to the long axis of the liquid crystal compound. However, strict parallelism is not required; in this specification, it refers to an alignment where the angle between the long axis of the liquid crystal compound and the main surface of the film is less than 10°. Similarly, in this specification, "vertical alignment" means that the main surface of the film is orthogonal to the long axis of the liquid crystal compound. However, strict perpendicularity is not required; in this specification, it refers to an alignment where the angle between the long axis of the liquid crystal compound and the main surface of the film is 170° to 110°.
[0330] Examples of phase retardation films of the present invention include positive A-plates, negative A-plates, positive C-plates, and optically anisotropic films (hereinafter, this method will also be referred to as "optically anisotropic film A"). These optically anisotropic films have, in the thickness direction: a first region formed by fixing the orientation of a liquid crystal compound twisted along a helical axis extending in the thickness direction; and a second region formed by fixing the orientation of a homogeneously oriented liquid crystal compound, preferably a positive A-plate or a negative A-plate.
[0331] The positive A-plate, negative A-plate, and positive C-plate are defined as follows.
[0332] When the refractive index along the slow axis (the direction with the highest refractive index in the plane) is set as nx, the refractive index along the direction orthogonal to the slow axis in the plane is set as ny, and the refractive index along the thickness direction is set as nz, the positive A plate satisfies equation (A1), the negative A plate satisfies equation (A2), and the positive C plate satisfies equation (C1). Furthermore, Rth for the positive A and positive C plates represents a positive value, while Rth for the negative A plate represents a negative value. Equation (A1) nx>ny≈nz Equation (A2) ny<nx≈nz Equation (C1) nz>nx≈ny
[0333] Furthermore, the above "≈" not only includes cases where the two are completely identical, but also cases where the two are substantially identical.
[0334] Regarding the phrase "substantially identical," in the positive A-plate, for example, the case where (ny-nz)×d (where d is the film thickness) is -10 to 10 nm, preferably -5 to 5 nm, is also included in "ny≈nz". Furthermore, in the negative A-plate, the case where (nx-nz)×d is -10 to 10 nm, preferably -5 to 5 nm, is also included in "nx≈nz". And in the positive C-plate, for example, the case where (nx-ny)×d (where d is the film thickness) is 0 to 10 nm, preferably 0 to 5 nm, is also included in "nx≈ny".
[0335] When the phase difference film of the present invention is a positive A plate, from the viewpoint of functioning as a λ / 4 plate, Re (550) is preferably 100 to 180 nm, more preferably 120 to 160 nm, even more preferably 130 to 150 nm, and especially preferably 130 to 145 nm.
[0336] Here, "λ / 4 plate" refers to a plate with λ / 4 function, specifically a plate that has the function of converting linearly polarized light of a specific wavelength into circularly polarized light (or converting circularly polarized light into linearly polarized light).
[0337] When the phase difference film of the present invention is a negative A plate, from the viewpoint of functioning as a λ / 2 plate, Re (550) is preferably 210 to 300 nm, more preferably 220 to 300 nm, even more preferably 220 to 280 nm, and especially preferably 220 to 260 nm.
[0338] The optical anisotropic film (optical anisotropic film A) is described in detail. The optical anisotropic film has the following in the thickness direction: a first region, which is formed by fixing the orientation state of a liquid crystal compound that is twisted along a helical axis extending in the thickness direction; and a second region, which is formed by fixing the orientation state of a homogeneously oriented liquid crystal compound.
[0339] With the thickness of the first region of the optical anisotropic film A set as d1 (nm) and the refractive index anisotropy of the first region measured at a wavelength of 550 nm set as Δn1, from the viewpoint that the optical anisotropic film can be appropriately applied to a circular polarizer, the first region preferably satisfies the following equation (1-1). Equation (1-1) 100nm≤Δn1d1≤240nm Among them, it is more preferable to satisfy equation (1-2), and even more preferable to satisfy equation (1-3). Equation (1-2) 120nm≤Δn1d1≤220nm Equation (1-3) 140nm≤Δn1d1≤200nm
[0340] In addition, the refractive index anisotropy Δn1 refers to the refractive index anisotropy of the first region.
[0341] The absolute value of the twist angle of the liquid crystal compound in the first region is not particularly limited, but from the viewpoint that the optical anisotropic film can be appropriately applied to a circular polarizer, it is preferably 60 to 120°, more preferably 70 to 110°. The twist angle was measured using Axometrics' AxoScan and its instrument analysis software.
[0342] Furthermore, if the thickness of the second region of the optical anisotropic film A is set to d2 (nm), and the refractive index anisotropy of the second region measured at a wavelength of 550nm is set to Δn2, from the viewpoint that the optical anisotropic film can be appropriately applied to a circular polarizer, the second region preferably satisfies the following formula (2-1). Equation (2-1) 100nm≤Δn2d2≤240nm Among them, it is more preferable to satisfy equation (2-2), and even more preferable to satisfy equation (2-3). Equation (2-2) 120nm≤Δn2d2≤220nm Equation (2-3) 140nm≤Δn2d2≤200nm
[0343] In addition, the refractive index anisotropy Δn2 refers to the refractive index anisotropy of the second region.
[0344] The retardation film of the present invention can exhibit either positive wavelength dispersion or inverse wavelength dispersion. Furthermore, the aforementioned positive wavelength dispersion and inverse wavelength dispersion are preferably exhibited in the visible light region.
[0345] Furthermore, the positive wavelength dispersion exhibited by the phase retardation film of the present invention means that the in-plane delay decreases as the measurement wavelength increases. Conversely, the inverse wavelength dispersion exhibited by the phase retardation film of the present invention means that the in-plane delay increases as the measurement wavelength increases.
[0346] The thickness of the phase retardation film of the present invention is not particularly limited, but is preferably 0.1 to 10 μm, more preferably 0.5 to 5 μm.
[0347] [Optical laminate]
[0348] The optical laminate of the present invention comprises a phase retardation layer and an adhesive layer (UV adhesive layer) formed by curing an ultraviolet-curable adhesive (UV adhesive), wherein, The aforementioned phase retardation layer comprises: a cured product of a free radical polymerizable liquid crystal compound (hereinafter also referred to as "cured product A"); and a cured product derived from a polymer (specific leveling agent) located on the side of the aforementioned UV adhesive layer (hereinafter also referred to as "cured product B"). The polymer has repeating units containing silicon atoms, repeating units containing cationic polymerizable groups, and repeating units containing free radical polymerizable groups.
[0349] Here, "cured material B is biased towards the UV adhesive layer side of the phase retardation layer" means that when the ion beam is irradiated from one surface of the phase retardation layer to the other, and the depth direction composition of the phase retardation layer is analyzed using time-of-flight secondary ion mass spectrometry, thereby obtaining the distribution curve of the secondary ion intensity X corresponding to the chemical structure of the cured material originating from a specific leveling agent in the depth direction, the amount of cured material B observed on the UV adhesive layer side surface of the phase retardation layer is more than 10 times the amount of cured material B observed at a depth of 100 nm from the UV adhesive layer side surface of the phase retardation layer.
[0350] The method for obtaining the above distribution curves using time-of-flight secondary ion mass spectrometry (TOF-SIMS) is described in detail.
[0351] First, the composition in the depth direction of the phasing layer is analyzed by TOF-SIMS while performing ion sputtering from one surface to the other.
[0352] Furthermore, the depth direction refers to the thickness direction of the phase difference layer. Specifically, regarding TOF-SIMS, it is described in "Surface Analysis Technology Series: Secondary Ion Mass Spectrometry" edited by the Japan Surface Science Society, published by Maruzen Co., Ltd. (1999).
[0353] By analyzing the composition in the depth direction of the phase difference layer, the distribution curve of the secondary ion intensity X (count / sec) of the chemical structure of the cured product derived from a specific leveling agent in the depth direction is obtained.
[0354] As an example of the aforementioned distribution curves, if the composition in the depth direction of the retardation layer is analyzed, a high secondary ion intensity X is initially observed, which gradually decreases with further depth. The secondary ion intensity X remains low with further depth. This indicates that the cured material originating from a specific leveling agent tends to be biased towards one surface side of the retardation layer.
[0355] The chemical structure of the cured product derived from a specific leveling agent that becomes the source of the secondary ionic strength X (hereinafter also referred to as "chemical structure XE") is not particularly limited as long as it is a chemical structure that allows for accurate determination of the distribution of the cured product derived from the specific leveling agent in the phase difference layer.
[0356] In addition, secondary ionic strength X refers to the strength of fragment ions originating from chemical structure XE.
[0357] Furthermore, while performing ion sputtering and analyzing the composition of the retardation layer along its depth direction using TOF-SIMS, the following series of operations are repeated: after analyzing the composition of a depth region of 1–2 nm, the depth is further expanded by 20 nm, and then the composition of the next depth region of 1–2 nm is analyzed. Therefore, the secondary ion intensity X at the aforementioned depth location refers to the result of the composition analysis of the aforementioned depth region of 1–2 nm.
[0358] The determination of TOF-SIMS is preferably carried out under the following determination conditions. Device used: TOF-SIMS V manufactured by ION-TOF Corporation Primary ion: Bi3 ++ (0.2pA) Measurement mode: Bunching mode, negative polarity Ion beam: Ar-GCIB gun (Ar 2000 + (15kV, 5.9nA, 500μm×500μm sputtering)
[0359] The aforementioned UV adhesive layer is a layer formed by curing an adhesive that can be cured by ultraviolet light, namely, an ultraviolet-curable adhesive (UV adhesive). Typically, it is a layer formed by curing an ultraviolet-curable adhesive (UV adhesive) layer (hereinafter also referred to as "UV adhesive composition layer").
[0360] Examples of UV adhesives include those containing cationic polymeric compounds and those containing free radical polymeric compounds. From the viewpoint of superior performance of the present invention, UV adhesives containing cationic polymeric compounds are preferred.
[0361] Furthermore, the aforementioned cationic polymerizable compounds are compounds having cationic polymerizable groups. Also, the aforementioned free radical polymerizable compounds are compounds having free radical polymerizable groups.
[0362] The definitions of cationic polymerizable groups and free radical polymerizable groups are as described above. Among them, the cationic polymerizable group is preferably an epoxy group. There are no particular limitations on the cationic polymerizable compound; examples include 1,4-butanediol diglycidyl ether, 2-ethylhexyl glycidyl ether, and 3,4-epoxycyclohexenylmethyl-3',4'-epoxycyclohexenylcarboxylate.
[0363] As a UV adhesive composition layer, reference can be made to paragraphs
[0062] to
[0080] of Japanese Patent Application Publication No. 2016-035579, the contents of which are incorporated herein by reference.
[0364] The optical laminate of the present invention can be formed by contacting the retardation film of the present invention with a UV adhesive and curing the UV adhesive by ultraviolet irradiation. Furthermore, the optical laminate of the present invention is typically a layer formed on the surface of a substrate by performing a UV adhesive curing process based on ultraviolet irradiation on a laminate comprising the retardation film, a UV adhesive composition layer, and the substrate, formed by laminating the retardation film of the present invention and the substrate (e.g., a film having a liquid crystal layer or a polarizer) via a UV adhesive. During this process, the polymerization reaction of the UV adhesive composition layer in the laminate occurs under ultraviolet irradiation, and polymerization also occurs between the UV adhesive composition layer and the cationic polymerizable groups of a specific leveling agent at the interface of the UV adhesive composition layer biased towards the retardation film. As a result, excellent adhesion exists between the retardation layer derived from the retardation film and the UV adhesive layer, which is the cured layer of the UV adhesive composition layer.
[0365] The optical laminate of the present invention may include layers other than the retardation layer and the UV bonding layer. Examples of such other layers include a support and an alignment film.
[0366] Figure 1 This is a schematic cross-sectional view illustrating an example of the optical laminate of the present invention. Additionally, Figure 1 For illustrative purposes only; the thickness and positional relationships of each layer may not necessarily match the actual dimensions. Figure 1 The support and orientation film shown are arbitrary components.
[0367] Figure 1 The optical laminate 10 shown sequentially comprises a support 12, an alignment film 14, a retardation layer 16, and a UV adhesive layer 18. The retardation layer 16 is a layer derived from the retardation film of the present invention, comprising a cured product of a free radical polymerizable liquid crystal compound (cured product A) and a cured product derived from a specific leveling agent that is biased towards the UV adhesive layer 18 (cured product B). Additionally, typically, a bonded material (not shown) is disposed on the side of the UV adhesive layer 18 opposite to the side of the retardation layer 16 of the optical laminate 10.
[0368] There are no particular limitations on the aforementioned substrate; for example, a film with a liquid crystal layer or a polarizer can be used.
[0369] Furthermore, the cured product A is a cured product obtained by free radical polymerization of the free radical polymerizable liquid crystal compound contained in the liquid crystal composition for manufacturing the retardation film of the present invention. Furthermore, the cured product B is a cured product obtained by free radical polymerization of a specific leveling agent contained in the liquid crystal composition for manufacturing the retardation film of the present invention.
[0370] For example, when the polarizer of the present invention described later is used as a circular polarizer, or when the optical laminate of the present invention is used as an optical compensation film in a liquid crystal display device of IPS (In-Plane-Switching) or FFS (Fringe-Field-Switching) mode, the optical laminate of the present invention preferably includes a positive A plate and a positive C plate. In this case, as Figure 2 and Figure 3 As shown, the optical laminate only needs to be configured to also include other liquid crystal layers. Furthermore, Figure 2 and Figure 3 For illustrative purposes only, the thickness and positional relationship of each layer may not be consistent with the actual situation.
[0371] Figure 2 The optical laminate 20 shown sequentially comprises a first adhesion layer 22, a retardation layer 24, a second adhesion layer 26, and a liquid crystal layer 28. One of the retardation layer 24 and the liquid crystal layer 28 is a positive A-plate, and the other is a positive C-plate. Furthermore, in the first adhesion layer 22 and the second adhesion layer 26, the layer opposite to the surface where the cured material B in the retardation layer 24 is located is a UV adhesive layer, and it is firmly bonded to the cationic polymeric groups of the retardation layer 24. Additionally, typically, a polarizer (not shown) is disposed on the side of the first adhesion layer 22 of the optical laminate 20 opposite to the side opposite to the retardation layer 24.
[0372] exist Figure 2 In the optical laminate 20 shown, the phase retardation layer 24 is preferably the positive A plate, and the liquid crystal layer 28 is the positive C plate.
[0373] Furthermore, in Figure 2 In the optical laminate 20 shown, the layer opposite to the surface side where the cured material B in the phase difference layer 24 is located is preferably the second adhesion layer 26, which is a UV adhesive layer.
[0374] Both the first adhesion layer 22 and the second adhesion layer 26 can be UV adhesive layers, or one of them can be an adhesive layer.
[0375] Figure 3 The optical laminate 30 shown sequentially comprises a first adhesion layer 22, a liquid crystal layer 28, a second adhesion layer 26, and a retardation layer 24. One of the retardation layer 24 and the liquid crystal layer 28 is a positive A-plate, and the other is a positive C-plate. Furthermore, the second adhesion layer 26 is a UV adhesive layer, firmly bonded to cationic polymeric groups derived from cured material B on the surface of the second adhesion layer 26 biased towards the retardation layer 24. Additionally, typically, a polarizer (not shown) is disposed on the side of the first adhesion layer 22 of the optical laminate 30 opposite to the side opposite to the liquid crystal layer 28.
[0376] The first adhesion layer 22 can be entirely a UV adhesive layer, or one of them can be an adhesive layer.
[0377] The various components used in the laminate of the present invention will be described in detail below.
[0378] [Support]
[0379] The support is a substrate used to support the phase difference layer.
[0380] The aforementioned support is preferably transparent. Specifically, the light transmittance is preferably 80% or higher.
[0381] Examples of supports include glass substrates and polymer films. Examples of polymer film materials include cellulose polymers; acrylic polymers containing acrylate polymers such as polymethyl methacrylate and polymers containing lactone rings; thermoplastic norbornene polymers; polycarbonate polymers; polyester polymers such as polyethylene terephthalate and polyethylene naphthalate; styrene polymers such as polystyrene and acrylonitrile-styrene copolymers (AS resins); polyolefin polymers such as polyethylene, polypropylene, and ethylene-propylene copolymers; vinyl chloride polymers; amide polymers such as nylon and aromatic polyamides; imide polymers; sulfone polymers; polyethersulfone polymers; polyetheretherketone polymers; polyphenylene sulfide polymers; vinylidene chloride polymers; vinyl alcohol polymers; vinyl butyral polymers; aromatic ester polymers; polyoxymethylene polymers; epoxy polymers; and polymers composed of mixtures of these polymers.
[0382] Furthermore, the polarizer described later can also serve as this support.
[0383] The thickness of the aforementioned support is not particularly limited, but is preferably 5–100 μm, more preferably 5–50 μm. The support is preferably peelable.
[0384] [Orientation film]
[0385] The optical laminate of the present invention may have an alignment film between the support and the retardation layer. Alternatively, the support may also serve as the alignment film.
[0386] Alignment films are typically composed primarily of polymers. Polymer materials used in alignment films are documented in numerous publications, and many commercially available products are readily available.
[0387] The polymer materials used in this invention are preferably polyvinyl alcohol or polyimide, and their derivatives. In particular, modified or unmodified polyvinyl alcohol is preferred.
[0388] Regarding the alignment film that can be used in this invention, examples include the alignment film described on page 43, line 24 to page 49, line 8 of International Publication No. 01 / 088574; the modified polyvinyl alcohol described in paragraphs
[0071] to
[0095] of Japanese Patent No. 3907735; the liquid crystal alignment film formed by a liquid crystal alignment agent described in Japanese Patent Application Publication No. 2012-155308; and so on.
[0389] In this invention, since the alignment film is not in contact with the surface of the alignment film during formation, planar degradation can be prevented. Therefore, photoalignment film is also preferred as the alignment film.
[0390] There are no particular restrictions on the photoalignment film, and polymer materials such as polyamide compounds or polyimide compounds described in paragraphs
[0024] to
[0043] of International Publication No. 2005 / 096041 can be used; liquid crystal alignment films formed from liquid crystal alignment agents having photoalignment groups with cinnamic acid structures as described in Japanese Patent Application Publication No. 2012-155308; and products manufactured by Rolic Technologies under the trade name LPP-JP265CP, etc.
[0391] Furthermore, in this invention, the thickness of the orientation film is not particularly limited, but from the viewpoint of mitigating the surface irregularities that may exist on the support and forming an optically anisotropic layer with uniform film thickness, it is preferably 0.01 to 10 μm, more preferably 0.01 to 1 μm, and even more preferably 0.01 to 0.5 μm.
[0392] [UV adhesive layer]
[0393] The thickness of the UV adhesive layer is preferably 0.01 to 20 μm, more preferably 0.01 to 10 μm, and even more preferably 0.05 to 5 μm. If the thickness of the UV adhesive layer is within this range, no lifting or peeling will occur between the laminated film and the polarizer, resulting in practically problem-free adhesion. Furthermore, from the viewpoint of suppressing bubble formation, the thickness of the adhesive layer is preferably 0.4 μm or more.
[0394] [Adhesive layer]
[0395] The optical laminate and polarizer of the present invention may have an adhesive layer as an attachment layer.
[0396] Examples of adhesives included in the adhesive layer include acrylic adhesives, epoxy adhesives, rubber adhesives, silicone adhesives, polyurethane adhesives, vinyl alkyl ether adhesives, polyvinyl alcohol adhesives, polyvinylpyrrolidone adhesives, polyacrylamide adhesives, and cellulose adhesives.
[0397] Among them, acrylic adhesives (pressure-sensitive adhesives) are preferred from the perspective of their superior transparency, weather resistance and heat resistance.
[0398] As an adhesive, reference can be made to paragraphs
[0071] to
[0084] of Japanese Patent Application Publication No. 2018-060014, the contents of which are incorporated herein by reference.
[0399] The thickness of the adhesive layer is preferably 0.01 to 20 μm, more preferably 0.01 to 10 μm, and even more preferably 0.05 to 5 μm. If the thickness of the adhesive layer is within this range, no lifting or peeling will occur between the laminated layers, and practically problem-free adhesion can be obtained.
[0400] The optical laminate of the present invention also preferably includes an ultraviolet (UV) absorber from the viewpoint of taking into account the effects of external light (especially ultraviolet light).
[0401] The ultraviolet absorber can be contained in the retardation layer or in components other than the retardation layer. A support is a preferred example of a component other than the retardation layer.
[0402] As a UV absorber, any existing known UV absorber capable of exhibiting UV absorption properties can be used. Among such UV absorbers, from the viewpoint of high UV absorption and obtaining UV absorption capacity (UV blocking capacity) for use in image display devices, benzotriazole or hydroxyphenyltriazine UV absorbers are preferred.
[0403] Furthermore, in order to broaden the absorption width of ultraviolet light, it is possible to use two or more ultraviolet absorbers with different maximum absorption wavelengths.
[0404] As ultraviolet absorbers, examples include compounds described in paragraphs
[0258] to
[0259] of Japanese Patent Application Publication No. 2012-018395 and compounds described in paragraphs
[0055] to
[0105] of Japanese Patent Application Publication No. 2007-072163.
[0405] Furthermore, as a commercially available product, it can be used with Tinuvin 400, Tinuvin 405, Tinuvin 460, Tinuvin 477, Tinuvin 479 and Tinuvin 1577 (all manufactured by BASF).
[0406] [Polarizing filter]
[0407] The polarizer of the present invention has a polarizer and the optical laminate of the present invention.
[0408] When the phase difference layer included in the optical laminate of the present invention is a positive A plate, from the viewpoint that it can be appropriately applied to circular polarizers, the angle between the slow axis of the positive A plate and the absorption axis of the polarizer described later is preferably 30 to 60°, more preferably 40 to 50°, even more preferably 42 to 48°, and particularly preferably 45°.
[0409] Here, "slow axis" refers to the direction with the highest refractive index in the plane of the phase difference layer, and "absorption axis" of the polarizer refers to the direction with the highest absorbance.
[0410] Furthermore, polarizers can also be used as optical compensation films in IPS or FFS liquid crystal display devices.
[0411] When using polarizers as optical compensation films in IPS or FFS type liquid crystal display devices, appropriate use is possible. Figure 2 and Figure 3 The optical laminate shown. Preferably, the slow axis of the positive A-plate layer is orthogonal or parallel to the absorption axis of the polarizer described later. More specifically, the angle between the slow axis of the positive A-plate layer and the absorption axis of the polarizer described later is 0 to 5° or 85 to 95°.
[0412] When the polarizer of the present invention is used in the image display device described later, the angle between the slow axis of the liquid crystal layer and the absorption axis of the polarizer described later is preferably parallel or orthogonal.
[0413] Figure 4 This is a schematic cross-sectional view illustrating an example of the polarizer of the present invention. Figure 4 The polarizer 40 shown has a polarizer 42 and an optical stack 20 (reference). Figure 2 ).in addition, Figure 4 For illustrative purposes only, the thickness and positional relationship of each layer may not be consistent with the actual situation. Furthermore, one of the first attachment layer 24 and the second attachment layer 28, as well as the liquid crystal layer, are arbitrary components. A protective film may be disposed on at least one surface of the polarizer 42. The material used for the protective film can be the same as that used for the support described above.
[0414] [Polarizer]
[0415] There are no particular restrictions on a polarizer as long as it is a component that has the function of converting light into specific linearly polarized light. Existing known absorption polarizers, reflection polarizers, and coating polarizers can be used.
[0416] As an absorption-type polarizer, iodine-based polarizers, dye-based polarizers utilizing dichroic dyes, and polyene-based polarizers can be used. Iodine-based polarizers and dye-based polarizers include coated polarizers and stretched polarizers, both of which can be used, but polarizers made by adsorbing iodine or dichroic dyes onto polyvinyl alcohol and then stretching them are preferred.
[0417] Examples of coating-type polarizers include polarizers containing cured liquid crystal compounds and dichroic pigments.
[0418] As a reflective polarizer, polarizers can be made by stacking thin films with different birefringence, wire grid polarizers, and polarizers that combine a cholesteric liquid crystal with a selective reflection region with a quarter-wave plate.
[0419] There is no particular limitation on the thickness of the polarizer, but it is preferably 3 to 60 μm, more preferably 3 to 30 μm, and even more preferably 3 to 10 μm.
[0420] [Image display device]
[0421] The display device of the present invention is an image display device having the film or polarizer of the present invention.
[0422] There are no particular limitations on the display elements used in the image display device. Examples include liquid crystal cells, organic electroluminescent (hereinafter referred to as "EL"). and plasma display panels. Among these, liquid crystal cells or organic EL display panels are preferred. That is, as the image display device of the present invention, a liquid crystal display device using liquid crystal cells as display elements and an organic EL display device using organic EL display panels as display elements are preferred.
[0423] [Organic EL display device]
[0424] As an example of an image display device, an organic EL display device may be arranged such that, from the viewing side, it has a polarizer, a λ / 4 plate formed by the aforementioned film, and an organic EL display panel in sequence.
[0425] Furthermore, an organic EL display panel is a display panel constructed using organic EL elements that sandwich an organic light-emitting layer (organic electroluminescent layer) between electrodes (between the cathode and the anode). There are no particular limitations on the construction of an organic EL display panel, and known constructions can be used.
[0426] [Liquid Crystal Display Device]
[0427] As an example of an image display device, a liquid crystal display device is a liquid crystal display device having the aforementioned polarizer and liquid crystal unit.
[0428] Furthermore, among the polarizers disposed on both sides of the liquid crystal cell, it is preferable to use the aforementioned polarizer as the front polarizer, and more preferably to use the aforementioned polarizer as both the front and back polarizers.
[0429] <Liquid Crystal Unit>
[0430] The liquid crystal cells used in the liquid crystal display device are preferably in VA (Vertical Alignment) mode, OCB (Optically Compensated Bend) mode, IPS (In-Plane-Switching) mode, FFS (Fringe-Field-Switching) mode or TN (Twisted Nematic) mode, but are not limited to these.
[0431] Example
[0432] The present invention will now be described in more detail based on embodiments. The materials, amounts, proportions, processing contents, and processing steps shown in the following embodiments can be appropriately modified without departing from the spirit of the invention. Therefore, the scope of the present invention should not be interpreted as limiting by the embodiments shown below.
[0433] [Example 1]
[0434] The positive A plate (phase retardation film) and the polarizer with the positive A plate were fabricated as follows.
[0435] [Fabrication of the support structure]
[0436] The following composition was added to a mixing tank and stirred, then heated at 90°C for 10 minutes. The resulting composition was then filtered through filter paper with an average pore size of 34 μm and a sintered metal filter with an average pore size of 10 μm to prepare a paste. The paste had a solids concentration of 23.5% by mass, the amount of plasticizer added was relative to the cellulose acylate, and the solvent was dichloromethane / methanol / butanol = 81 / 18 / 1 (mass ratio). ―――――――――――――――――――――――――――――――― Cellulose acylated gel ―――――――――――――――――――――――――――――――― Cellulose acylates (Acetyl substitution degree 2.86, viscosity-uniform polymerization degree 310) 100 parts by weight • 6.0 parts by mass of sugar ester compound 1 (formula (S4) below) • Sugar ester compound 2 (formula (S5) below) 2.0 parts by mass • Silica particle dispersion (AEROSIL R972, manufactured by NIPPON AEROSIL CO., LTD.) 0.1 parts by weight • Solvent (dichloromethane / methanol / butanol) 351.9 parts by weight ――――――――――――――――――――――――――――――― [Chemical Formula 23] [Chemical Formula 24]
[0437] The adhesive paste prepared above was cast using a roller film casting machine. The adhesive paste was cast from the mold to contact a metal support cooled to 0°C, and then the resulting sheet (film) was peeled off from the roller. The roller was made of SUS (stainless steel).
[0438] After the film obtained by casting is peeled off from the roller, it is dried for 20 minutes in a tenter frame that holds both ends of the film at 30-40°C during film conveying. Then, the film is further dried by zone heating while being conveyed by rollers. The resulting film is then knurled and wound up to form cellulose acylated film A1.
[0439] The obtained cellulose acylated membrane A1 has a thickness of 60 μm, an in-plane retardation Re(550) of 1 nm at a wavelength of 550 nm, and a thickness retardation Rth(550) of 35 nm at a wavelength of 550 nm.
[0440] [Fabrication of photoalignment film 1]
[0441] The photo-alignment film forming coating solution E1, consisting of the following composition, is continuously coated onto the cellulose acylate film 1 using a wire rod. The support with the coated film is dried with hot air at 134°C for 75 seconds, and then the coating film is irradiated with polarized ultraviolet light (8 mJ / cm²). 2 Using an ultra-high pressure mercury lamp, photo-alignment film 1 was formed. The thickness of photo-alignment film 1 is 0.5 μm. ――――――――――――――――――――――――――――――― Coating solution E1 for photo-aligned film formation ――――――――――――――――――――――――――――――― • 100.00 parts by weight of the following polymer PA-1 • 6.00 parts by weight of the following acid-producing agent TAG-1 • 0.60 parts by weight of DIPEA ·Butyl acetate 625.4 parts by weight 156.3 parts by weight of methyl ethyl ketone ――――――――――――――――――――――――――――――― Polymer PA-1 [In the following formula, the value recorded in each repeating unit represents the content (mass%) of each repeating unit relative to all repeating units. Weight-average molecular weight: 45000] [Chemical Formula 25] Acid-producing agent TAG-1 [Chemical Formula 26] DIPEA [Chemical Formula 27]
[0442] [Fabrication of Positive A-plate (phase retardation film)]
[0443] The composition F1-1 with the following structure was applied onto the photoalignment film E1 using a bar coater.
[0444] The coating formed on the photoalignment film E1 was heated to 120°C with hot air, then cooled to 60°C, and then irradiated with a high-pressure mercury lamp at a wavelength of 365 nm and a dose of 100 mJ / cm under a nitrogen atmosphere. 2 The coating was irradiated with ultraviolet light, and then heated to 120°C while being irradiated with an irradiation dose of 500 mJ / cm. 2 By irradiating the coating with ultraviolet light, the orientation of the liquid crystal compound is fixed, thereby producing an optical film F1-1 with a positive A plate F1-1.
[0445] The thickness of plate A, F1-1, is 2.5 μm, and Re(550) is 144 nm. Furthermore, plate A satisfies the relationship Re(450) ≤ Re(550) ≤ Re(650). Re(450) / Re(550) is 0.82. The aforementioned plate A is equivalent to a so-called λ / 4 plate. ―――――――――――――――――――――――――――――――― Composition F1-1 for forming positive A plate ―――――――――――――――――――――――――――――――― • 30.00 parts by weight of the following free radical polymerizable liquid crystal compound LA-1 • 30.00 parts by weight of the following free radical polymerizable liquid crystal compound LA-2 • 27.00 parts by weight of the following free radical polymerizable liquid crystal compound LA-3 • 8.00 parts by weight of the following free radical polymerizable liquid crystal compound LA-4 • 5.00 parts by weight of the following free radical polymerizable liquid crystal compound LA-5 • 0.55 parts by weight of the following free radical polymerization initiator PI-1 • The polymer (surfactant) KA-1 listed in Table 1 is 0.06 parts by weight. · Cyclopentanone 235.00 parts by weight ―――――――――――――――――――――――――――――――― LA-1, a free radical polymerizable liquid crystal compound (tBu represents tert-butyl). [Chemical Formula 28] Free radical polymerizable liquid crystal compound LA-2 [Chemical Formula 29] Free radical polymerizable liquid crystal compound LA-3 [Chemical Formula 30] Free radical polymerizable liquid crystal compound LA-4 [Chemical Formula 31] LA-5, a free radical polymerizable liquid crystal compound (Me represents methyl). [Chemical Formula 32] Polymerization initiator PI-1 [Chemical Formula 33]
[0446] [Making of Polarizing Filters]
[0447] <Fabrication of Polarizer 1 with Protective Film>
[0448] The surface of the support for the cellulose triacetate membrane TJ25 (manufactured by FUJIFILM Corporation: 25 μm thickness) was subjected to alkaline saponification treatment. Specifically, the support was immersed in a 1.5 equivalent concentration sodium hydroxide aqueous solution at 55°C for 2 minutes, then washed in a water bath at room temperature, and further neutralized with a 0.1 equivalent concentration sulfuric acid solution at 30°C. After neutralization, the support was washed in a water bath at room temperature and further dried with hot air at 100°C to obtain the polarizer protective film.
[0449] A roller-shaped polyvinyl alcohol film was stretched in an iodine aqueous solution along the MD (Machine Direction) direction and dried to obtain a polarizer 1 with a thickness of 14 μm.
[0450] The protective film of the polarizer was attached to the two sides of the polarizer 1 using PVA adhesive, thus creating a polarizer 1 with a protective film.
[0451] <Preparation of UV Adhesive 1>
[0452] A UV adhesive 1 with the following composition was prepared. ──────────────────────────────── UV adhesive 1 ──────────────────────────────── • CEL2021P (manufactured by Daicel Corporation) 70 parts by weight · 20 parts by weight of 1,4-Butanediol diglycidyl ether 10 parts by weight of 2-ethylhexyl glycidyl ether • CPI-100P 2.25 parts by weight ──────────────────────────────── CPI-100P [Chemical Formula 34]
[0453] <Making of Polarizing Sheets>
[0454] With a discharge rate of 125 W·min / m 2 The positive A-plate side surface of the aforementioned optical film F1-1 was subjected to corona treatment. Next, the corona-treated surface of the optical film F1-1 was bonded to the surface of the polarizer 1 with the protective film using the aforementioned UV adhesive 1. At this time, the bonding was performed such that the angle between the absorption axis of the polarizer included in the polarizer 1 with the protective film and the slow axis of the optical film F1-1 was 45°. Then, from the optical film F1-1 side, irradiation was performed at a wavelength of 365 nm and an irradiation dose of 150 mJ / cm². 2 By irradiating the coating with ultraviolet light, the orientation film of optical film F1-1 and cellulose acylate film A1 were removed, and polarizer F1-1 was obtained.
[0455] In addition, in the positive A plate of the polarizer, it was confirmed that the cured product of surfactant KA-1 was biased towards the surface of the UV adhesive layer side.
[0456] [Examples 2-9, 11-13]
[0457] Except for changing the type and amount of polymer (surfactant) KA-1 as described in Table 1, optical films F1-2 to F1-9 and F1-11 to F1-13 with positive A plates were produced by the same steps as optical film F1-1.
[0458] Furthermore, except for changing optical film F1-1 to optical films F1-2~F1-9 and F1-11~F1-13, polarizers F1-2~F1-9 and F1-11~F1-13 were manufactured using the same steps as polarizer F1-1.
[0459] In addition, in the positive A plate of each polarizer produced, it was confirmed that the cured surfactants (KA-2 to KA-9, KA-11 to 13) were biased towards the surface of the UV adhesive layer.
[0460] [Example 10]
[0461] [Fabrication of the support structure]
[0462] A strip of cellulose acylated membrane (TD80UL, manufactured by FUJIFILM Corporation) is passed through a dielectric heating roller at 60°C to raise the membrane surface temperature to 40°C. Then, an alkaline solution of the composition shown below is applied at a coating rate of 14 ml / m using a bar coater. 2 The coating was applied to the tape-side surface of the membrane and conveyed for 10 seconds using a steam-type far-infrared heater manufactured by NORITAKE CO., LIMITED, heated to 110°C. Then, using a bar coater, the membrane was coated at a rate of 3 ml / m². 2 Pure water was applied. Then, after three repeated water washings based on a fountain-type coating machine and dehydration based on an air knife, the membrane was conveyed to a drying zone at 70°C for 10 seconds and dried to produce an alkali-saponified cellulose acylate membrane B1 (thickness: 80 μm). ──────────────────────────────── Composition of alkaline solutions ──────────────────────────────── 4.7 parts by weight of potassium hydroxide 15.8 parts by weight of water 63.7 parts by weight of isopropanol Surfactant SF-1: C 14 H 29 O(CH2CH2O) 20 H 1.0 parts by weight 14.8 parts by weight of propylene glycol ────────────────────────────────
[0463] [Preparation of Orientation Film A]
[0464] Using a #14 wire rod, the following orientation film coating solution A was continuously coated onto the alkali-saponified surface of the cellulose acylate film B1. The coating was then dried with hot air at 60°C for 60 seconds, followed by drying with hot air at 100°C for 120 seconds to obtain orientation film A (thickness: 0.5 μm). ―――――――――――――――――――――――――――――― Composition of Orientation Film Coating Solution A ―――――――――――――――――――――――――――――― The following polyvinyl alcohol-1 10 parts by weight 371 parts by weight of water 119 parts by weight of methanol Glutaraldehyde (crosslinking agent) 0.5 parts by weight Citrate ester (manufactured by SANKYO CHEMICAL Co., Ltd.) 0.175 parts by weight ―――――――――――――――――――――――――――――― Polyvinyl alcohol-1 [In the following formula, the values recorded in each repeating unit represent the content (mass%) of each repeat relative to all repeating units.] [Chemical Formula 35]
[0465] The orientation film A produced above was continuously subjected to friction treatment. At this time, the length direction of the elongated film is parallel to the conveying direction, and the angle between the length direction of the film and the rotation axis of the friction roller is set to 72.5° (with the width direction of the film set to 0° and the length direction of the film set to 90°, when viewed from the side of orientation film A, with the width direction as the reference and a positive value representing the clockwise direction, the rotation axis of the friction roller is -17.5°).
[0466] [Fabrication of the negative A-plate (phase retardation film)]
[0467] Using a #4.8 wire rod, the negative A-plate forming composition F1-10, consisting of the following components, is continuously coated onto the alignment film A prepared above. The film transport speed is set to 26 m / min. To dry the solvent of the coating solution and ripen the orientation of the disc-shaped liquid crystal compound, the coating on the alignment film A is heated with hot air at 130°C for 90 seconds, followed by heating with hot air at 100°C for 60 seconds, and then irradiated at 80°C with an irradiation dose of 300 mJ / cm. 2By subjecting the liquid crystal compound to UV (ultraviolet) irradiation, the orientation of the liquid crystal compound was fixed, thereby creating an optical film F1-10 with a negative A plate F1-10.
[0468] The thickness of the negative A plate F1-10 is 2.0 μm. Furthermore, it was confirmed that the average tilt angle of the disk-shaped liquid crystal compound relative to the film surface is 90°, and the disk-shaped liquid crystal compound is perpendicularly oriented relative to the film surface. Moreover, the angle of the slow axis is parallel to the rotation axis of the friction roller, and if the film width direction is set to 0° (and the film length direction is set to 90°, viewed from the negative A plate F1-10 side, with the film width direction as the reference, a positive value is used to represent the clockwise direction), it is -17.5°. Furthermore, the in-plane retardation of the negative A plate F1-10 at a wavelength of 550 nm is 240 nm. The negative A plate F1-10 exhibits positive wavelength dispersion. Furthermore, the aforementioned negative A plate is equivalent to a so-called λ / 2 plate. ―――――――――――――――――――――――――――――――― Composition of composition F1-10 for forming negative A plate ―――――――――――――――――――――――――――――――― The following free radical polymerizable disk-shaped liquid crystal-1 80 parts by weight The following free radical polymerizable disk-shaped liquid crystal-2, 20 parts by weight The following orientation film interface orientation agent-1 2 parts by weight The polymer (surfactant) KA-10 listed in Table 1 is 0.35 parts by weight. 5 parts by weight of ethylene oxide modified trimethylolpropane triacrylate Photopolymerization initiator (Omnirad 907, manufactured by IGM Resins BV) 4 parts by weight 200 parts by weight of methyl ethyl ketone ―――――――――――――――――――――――――――――――― Free radical polymerizable disk-shaped liquid crystal-1 [Chemical Formula 36] Free radical polymerizable disk-shaped liquid crystal-2 [Chemical Formula 37] Orientation film interface orientation agent-1 [Chemical Formula 38]
[0469] [Making of Polarizing Filters]
[0470] Using the polarizer 1 with protective film and UV adhesive 1 prepared in the above section, polarizer F1-10 was fabricated as follows.
[0471] With a discharge rate of 125 W·min / m 2 The negative A-plate side surface of the aforementioned optical film F1-10 was subjected to corona treatment. Next, the corona-treated surface of the optical film F1-10 was bonded to the surface of the polarizer 1 with the protective film using the aforementioned UV adhesive 1. At this time, the bonding was performed such that the angle between the absorption axis of the polarizer included in the polarizer 1 with the protective film and the slow axis of the optical film F1-10 was 45°. Then, from the optical film F1-10 side, irradiation was applied at a wavelength of 365 nm and an irradiation dose of 150 mJ / cm². 2 By irradiating the coating with ultraviolet light, the orientation film and cellulose acylate film B1 of the optical film F1-10 were removed, and the polarizer F1-10 was obtained.
[0472] In addition, in the negative A plate of the fabricated polarizer, it was confirmed that the cured surfactant (KA-10) was biased towards the surface of the UV adhesive layer.
[0473] [Comparative Example 1]
[0474] Except for changing the type and amount of polymer (surfactant) KA-1 as described in Table 1, optical film F1-R with a positive A plate was produced by the same steps as optical film F1-1.
[0475] Furthermore, except for changing the optical film F1-1 to the optical film F1-R, the polarizer F1-R was manufactured using the same steps as the polarizer F1-1.
[0476] [evaluate]
[0477] [Adhesion]
[0478] Adhesion was evaluated using the cross-cut method as described in JIS-K-5600-5-6-1.
[0479] In each of the fabricated polarizers, 100 squares were drawn at 1mm intervals on the surface of the optical film, and an adhesion test was conducted using cellophane tape (manufactured by NICHIBAN CO., LTD.). The cellophane tape application and removal were repeated three times, and after the third removal, the results were evaluated according to the following criteria. The squares were created by forming cuts from the retardation layer side to the interior of the UV adhesive layer. Furthermore, if the evaluation result is any one of evaluations A to D, there is no practical problem; evaluation A is preferred. "A": The number of cells in the grid that have not been peeled off is 90-100. "B": The number of squares that have not been peeled off is 70-89. "C": The number of cells that have not been peeled off is 50-69. "D": The number of cells in the grid that have not been peeled off is 30-49. “E”: The number of cells that have not been peeled is 29 or less.
[0480] [Orientation and planarity]
[0481] In the backlight, two polarizers 1 with protective films were arranged orthogonally to each other. Between them, the optical films (F1-1 to F1-13, F1-R) of the embodiment and comparative example were arranged with the angle between the absorption axis of the polarizer 1 and the slow axis of each optical film being 45° and observed.
[0482] As a result, it was confirmed that each optical film was observed to be in a uniform state, and that the orientation and planarity were at a level that was practically problem-free.
[0483] Table 1 is shown below.
[0484] The content (mass%) of each repeating unit in the “Polymer Composition” column of Table 1 represents the content (mass%) relative to all repeating units.
[0485] The types of repeating units in the "Polymer Composition" column of Table 1 are as follows.
[0486] In addition, in each repeating unit from P-1 to P-3, the lengths (lengths Ar) of the unsaturated double bond groups contained in the main chain to the free radical polymerizable groups are 6 atoms, 8 atoms, and 7 atoms, respectively.
[0487] Furthermore, in each repeating unit of Ep-1 and Ep-2, the length (length Ak) from the main chain to the cationic polymeric group is 3 atoms and 8 atoms, respectively.
[0488] [Chemical Formula 39] [Chemical Formula 40] [Chemical Formula 41] [Chemical Formula 42]
[0489]
[0490] As can be seen from the results in Table 1, the phase difference film of the embodiment exhibits excellent adhesion to the UV adhesive layer formed by the curing of the UV adhesive when it is in contact with the UV adhesive and subjected to UV adhesive curing treatment based on ultraviolet irradiation.
[0491] Furthermore, a comparison of Examples 1 to 4 confirms that when the polymer (specific leveling agent) is a repeating unit containing silicon atoms and includes repeating units having groups represented by formula (Ia-1) with m representing 3, or repeating units having groups represented by formula (1b), the adhesion between the phase difference film and the UV adhesive layer is superior.
[0492] Furthermore, a comparison of Examples 2, 5, and 6 and Examples 7 to 9 confirmed that when the polymer (specific leveling agent) contains a free radical polymerizable group having an unsaturated double bond group, and the repeating unit containing the free radical polymerizable group has a length (length Ar) of 7 or more atoms from the main chain to the free radical polymerizable group, the adhesion between the phase difference film and the UV adhesive layer is better.
[0493] Furthermore, a comparison of Examples 2 and 7 confirms that when the polymer (specific leveling agent) contains repeating units with a length of 8 atoms or more from the main chain to the cationic polymeric group as repeating units containing cationic polymeric groups, the adhesion between the phase difference film and the UV adhesive layer is superior.
[0494] Furthermore, a comparison of Examples 2 and 11 confirms that when the content of repeating units containing silicon atoms in the polymer (specific leveling agent) is 50% by mass or more relative to all repeating units of the polymer, the adhesion between the phase difference film and the UV adhesive layer is superior.
[0495] Furthermore, a comparison of Examples 2 and 12 confirms that when the content of repeating units containing free radical polymerizable groups in the polymer (specific leveling agent) is 5% by mass or more relative to all repeating units of the polymer, the adhesion between the phase difference film and the UV adhesive layer is superior.
[0496] Furthermore, a comparison of Examples 2 and 13 confirmed that when the content of repeating units containing cationic polymeric groups in the polymer (specific leveling agent) is 5% by mass or more relative to all repeating units of the polymer, the adhesion between the phase difference film and the UV adhesive layer is superior.
[0497] Symbol Explanation 10, 20, 30 - Optical laminate, 12 - Support, 14 - Alignment film, 16, 24 - Phase retardation layer, 18 - UV adhesive layer, 22 - First adhesion layer, 26 - Second adhesion layer, 24 - Phase retardation layer, 28 - Liquid crystal layer, 40 - Polarizer, 42 - Polarizer.
Claims
1. A phase retardation film, which is obtained by free radical polymerization of a composition comprising a free radical polymerizable liquid crystal compound and a polymer, wherein, The polymer has repeating units containing silicon atoms, repeating units containing cationic polymeric groups, and repeating units containing free radical polymeric groups.
2. The phase retardation film according to claim 1, wherein, The repeating unit containing silicon atoms has a group represented by formula (Ia-1), [Chemical Formula 1] R A Each can independently represent an alkyl, alkenyl, aryl, or aralkyl group that may have substituents, L A This represents an m+1 valence linker, where m represents 2 or 3. Indicates the bonding location.
3. The phase retardation film according to claim 1 or 2, wherein, The repeating unit containing silicon atoms has a group represented by formula (Ib). [Chemical Formula 2] R B Each can independently represent an alkyl, alkenyl, aryl, or aralkyl group that may have substituents, and n represents a number greater than 2. Indicates the bonding location.
4. The phase retardation film according to claim 1 or 2, wherein, In the repeating unit containing a free radical polymerizable group, the free radical polymerizable group is a polymerizable group having an unsaturated double bond group, and the length from the main chain to the unsaturated double bond group contained in the free radical polymerizable group is 7 atoms or more.
5. The phase retardation film according to claim 1 or 2, wherein, The repeating unit containing the free radical polymerizable group is a repeating unit represented by formula (Z-1). [Chemical Formula 3] In equation (Z-1), D 1 Represents hydrogen atom, methyl group, -CH2OR Z1 or -CH2COOR Z2 R Z1 R represents an alkyl group having 1 to 4 hydrogen atoms or carbon atoms. Z2 A represents a hydrogen atom or a methyl group. 1 Indicates -O- or -NR Z3 -, R Z3 The letter indicates an alkyl group with 1 to 4 hydrogen or carbon atoms, w indicates an integer from 2 to 5, and L represents an alkyl group with 1 to 4 hydrogen or carbon atoms. Z1 This indicates a w+1 valence linker having at least one of the groups selected from aliphatic and aromatic groups; however, among the aliphatic groups, at least one -CH2- can be -NR. Z4 -, -O-, -S-, -CO-, -SO-, or -SO2- can be substituted; at least one -CH2CH2- can be substituted by -N=N- or -CH=N-; at least one -CH< can be substituted by -N<; R Z4 It represents an alkyl group having 1 to 4 hydrogen atoms or carbon atoms, in the presence of multiple R... Z4 In the case of multiple R Z4 They can be the same or different, L Z2 Indicates a single bond or a bond selected from alkylene, arylene, -CO-, -O-, and -NR. Z5 - At least one of the divalent linkers in the group, R Z5 It represents an alkyl group having 1 to 4 hydrogen atoms or carbon atoms, in the presence of multiple R... Z5 In the case of multiple R Z5 They can be the same or different; there can be multiple Ls. Z2 They can be the same or different, E 1 The E represents a group represented by formula (Ea-1) or a group represented by formula (Ea-2), and there are multiple E's. 1 They can be the same as each other, or they can be different. [Chemical Formula 4] In equation (Ea-1), R E1 Each of the hydrogen atom and the methyl group can be represented independently, in formula (Ea-2), R E2 Each can be used independently to represent a hydrogen atom or a methyl group, R E3 Representing an alkyl group having 1 to 4 hydrogen atoms, in formulas (Ea-1) and (Ea-2), Indicates the bonding location.
6. The phase retardation film according to claim 1 or 2, wherein, In the repeating unit containing the cationic polymerizable group, the length from the main chain to the cationic polymerizable group is 8 atoms or more.
7. The phase retardation film according to claim 1 or 2, wherein, The free radical polymerizable liquid crystal compound is at least one of the following selected from the group consisting of free radical polymerizable rod-shaped liquid crystal compounds and free radical polymerizable disk-shaped liquid crystal compounds.
8. The phase retardation film according to claim 1 or 2, wherein, In the polymer, The content of the repeating units containing silicon atoms is 30-80% by mass relative to the total number of repeating units in the polymer. The content of the repeating unit containing the cationic polymeric group is 3-30% by mass relative to the total number of repeating units in the polymer. The content of the repeating unit containing the free radical polymerizable group is 3 to 30 by mass relative to the total number of repeating units of the polymer.
9. The phase retardation film according to claim 1 or 2, wherein, In the polymer, The content of the repeating units containing silicon atoms is 50-70% by mass relative to all repeating units of the polymer. The content of the repeating unit containing cationic polymeric groups is 5-15% by mass relative to the total number of repeating units in the polymer. The content of the repeating unit containing the free radical polymerizable group is 5 to 15 by mass relative to the total number of repeating units of the polymer.
10. An optical laminate comprising a retardation layer and an adhesive layer cured with a UV-curable adhesive, wherein, The phase difference layer comprises: a cured product of a free radical polymerizable liquid crystal compound; and a cured product derived from a polymer biased towards the adhesive layer side, the polymer having repeating units comprising silicon atoms, repeating units comprising cationic polymerizable groups, and repeating units comprising free radical polymerizable groups.
11. The optical laminate according to claim 10, wherein, The adhesive layer is formed by curing an ultraviolet-curable adhesive containing an epoxy compound, and the cationic polymeric groups contained in the polymer are epoxy groups.
12. The optical laminate according to claim 10 or 11, wherein, The repeating unit containing silicon atoms contained in the polymer has a group represented by formula (Ia-1). [Chemical Formula 5] R A Each can independently represent an alkyl, alkenyl, aryl, or aralkyl group that may have substituents, L A This represents an m+1 valence linker, where m represents 2 or 3. Indicates the bonding location.
13. The optical laminate according to claim 10 or 11, wherein, The repeating units containing silicon atoms contained in the polymer have groups represented by formula (Ib). [Chemical Formula 6] R B Each can independently represent an alkyl, alkenyl, aryl, or aralkyl group that may have substituents, and n represents a number greater than 2. Indicates the bonding location.
14. The optical laminate according to claim 10 or 11, wherein, In the repeating unit containing a free radical polymerizable group, the free radical polymerizable group is a polymerizable group having an unsaturated double bond group, and the length from the main chain to the unsaturated double bond group contained in the free radical polymerizable group is 7 atoms or more.
15. The optical laminate according to claim 10 or 11, wherein, The repeating unit containing free radical polymerizable groups contained in the polymer is a repeating unit represented by formula (Z-1). [Chemical Formula 7] In equation (Z-1), D 1 Represents hydrogen atom, methyl group, -CH2OR Z1 or -CH2COOR Z2 R Z1 R represents an alkyl group having 1 to 4 hydrogen atoms or carbon atoms. Z2 A represents a hydrogen atom or a methyl group. 1 Indicates -O- or -NR Z3 -, R Z3 The letter indicates an alkyl group with 1 to 4 hydrogen or carbon atoms, w indicates an integer from 2 to 5, and L represents an alkyl group with 1 to 4 hydrogen or carbon atoms. Z1 This indicates a w+1 valence linker having at least one of the groups selected from aliphatic and aromatic groups; however, among the aliphatic groups, at least one -CH2- can be -NR. Z4 -, -O-, -S-, -CO-, -SO-, or -SO2- can be substituted; at least one -CH2CH2- can be substituted by -N=N- or -CH=N-; at least one -CH< can be substituted by -N<; R Z4 It represents an alkyl group having 1 to 4 hydrogen atoms or carbon atoms, in the presence of multiple R... Z4 In the case of multiple R Z4 They can be the same or different, L Z2 Indicates a single bond or a bond selected from alkylene, arylene, -CO-, -O-, and -NR. Z5 - At least one of the divalent linkers in the group, R Z5 It represents an alkyl group having 1 to 4 hydrogen atoms or carbon atoms, in the presence of multiple R... Z5 In the case of multiple R Z5 They can be the same or different; there can be multiple Ls. Z2 They can be the same or different, E 1 The E represents a group represented by formula (Ea-1) or a group represented by formula (Ea-2), and there are multiple E's. 1 They can be the same as each other, or they can be different. [Chemical Formula 8] In equation (Ea-1), R E1 Each of the hydrogen atom and the methyl group can be represented independently, in formula (Ea-2), R E2 Each can be used independently to represent a hydrogen atom or a methyl group, R E3 Representing an alkyl group having 1 to 4 hydrogen atoms, in formulas (Ea-1) and (Ea-2), Indicates the bonding location.
16. The optical laminate according to claim 10 or 11, wherein, In the repeating unit containing cationic polymeric groups contained in the polymer, the length from the main chain to the cationic polymeric group is 8 atoms or more.
17. The optical laminate according to claim 10 or 11, wherein, The free radical polymerizable liquid crystal compound is at least one free radical polymerizable liquid crystal compound selected from the group consisting of free radical polymerizable rod-shaped liquid crystal compounds and free radical polymerizable disk-shaped liquid crystal compounds.
18. The optical laminate according to claim 10 or 11, wherein, In the polymer, The content of the repeating units containing silicon atoms is 30-80% by mass relative to the total number of repeating units in the polymer. The content of the repeating unit containing the cationic polymeric group is 3-30% by mass relative to the total number of repeating units in the polymer. The content of the repeating unit containing the free radical polymerizable group is 3 to 30 by mass relative to the total number of repeating units of the polymer.
19. The optical laminate according to claim 10 or 11, wherein, In the polymer, The content of the repeating units containing silicon atoms is 50-70% by mass relative to all repeating units of the polymer. The content of the repeating unit containing cationic polymeric groups is 5-15% by mass relative to the total number of repeating units in the polymer. The content of the repeating unit containing the free radical polymerizable group is 5 to 15 by mass relative to the total number of repeating units of the polymer.
20. A polarizer having the optical laminate and polarizer as described in claim 10 or 11.
21. An image display device comprising the polarizer of claim 20.
22. The image display device according to claim 21, wherein it is an organic electroluminescent display device.
23. The image display device according to claim 21, wherein it is a liquid crystal display device.
Citation Information
Patent Citations
Static elimination lamp
JP1989088574A
polymerizable liquid crystal compound
JP1999513019A
Hydrophobic compound with excluded volume effect
JP2002020363A
Optical film, polarizing plate using the same, and liquid crystal display device
JP2004198511A
Liquid crystal compound, liquid crystyal composition, polymer, retardation plate, and elliptical polarization plate
JP2005289980A